Steel sheet, component and method for manufacturing thereof

CN122996218APending Publication Date: 2026-10-27JFE STEEL CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580023544.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-01-28
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0047]根据本发明,可以获得TS为1180MPa以上、YR为65%以上且延展性、剪切端面部的耐疲劳特性以及腐蚀环境下的耐延迟断裂特性优异的钢板。此外,通过将本发明的钢板应用于例如汽车结构部件,可以实现由车身轻量化带来的燃料效率的提高。因此,工业上的利用价值极大。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996218A_ABST
    Figure CN122996218A_ABST
Patent Text Reader

Abstract

The present invention provides a steel sheet, a member, and a method for manufacturing the same, the steel sheet having a tensile strength TS of 1180 MPa or more, a yield ratio YR of 65% or more, and excellent ductility, fatigue resistance of a sheared end surface portion, and delayed fracture resistance in a corrosive environment. The steel sheet of the present invention has a specific composition, and at a position of 1 / 4 of a sheet thickness, has a structure in which a tempered martensite amount is 83% or more in terms of an area fraction, a residual austenite amount is less than 3% in terms of a volume fraction, a total of a ferrite amount and a bainite ferrite amount is 5% or more and less than 15% in terms of an area fraction, an average of a lath bundle having a largest occupancy within a prior austenite grain at a center position of the sheet thickness of the steel sheet is set as P(C), and an average of an occupancy of the lath bundle having the largest occupancy within the prior austenite grain at a position of 100 μm in depth from a surface of the steel sheet is set as P(S), and satisfies P(C) ≤ 70% and {P(S) - P(C)} ≤ 20%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a steel plate, components, and a method for manufacturing the same, exhibiting excellent tensile strength, yield ratio, ductility, fatigue resistance at the shear end face, and resistance to delayed fracture in corrosive environments. The steel plate of this invention is suitable for use as structural components in automobiles and the like. Background Technology

[0002] To balance the goals of reducing CO2 emissions through vehicle lightweighting and improving crashworthiness through body lightweighting, the use of high-strength thin steel sheets in automobiles is constantly evolving, and new regulations are being introduced. Therefore, to improve body strength, the application of high-strength steel sheets with a tensile strength (TS) of 1180 MPa or higher in the main structural components of automobiles is increasing.

[0003] For high-strength steel sheets used in automobiles, excellent yield ratio, excellent ductility, excellent fatigue resistance at the shear end face, and excellent resistance to delayed fracture in corrosive environments are required. For example, in skeletal components such as automotive pillars, steel sheets with excellent ductility are preferred from a formability perspective. Furthermore, from a component performance perspective, excellent yield ratio, excellent fatigue resistance at the shear end face, and excellent resistance to delayed fracture in corrosive environments are also required.

[0004] Patent Document 1 discloses a high-strength steel plate with a yield ratio of 1180 MPa or higher, exhibiting excellent flatness in the width direction and resistance to processing embrittlement, as well as a method for manufacturing the same. However, the technology described in Patent Document 1 does not consider high-strength steel plates with excellent ductility, fatigue resistance at shear ends, and resistance to delayed fracture in corrosive environments.

[0005] Patent Document 2 discloses a high-strength steel plate with a strength of 1180 MPa or higher, exhibiting excellent ductility and resistance to flexural cracking at the shear end face, and a method for manufacturing the same. However, the technology described in Patent Document 2 does not consider high-strength steel plates with excellent fatigue resistance at the shear end face face and resistance to delayed fracture in corrosive environments.

[0006] Patent Document 3 discloses a high-strength steel plate with excellent surface properties, plate shape, and fatigue strength of 980 MPa or higher, and a method for manufacturing the same. However, the technology described in Patent Document 3 does not consider high-strength steel plates with excellent ductility, fatigue resistance at shear ends, and resistance to delayed fracture in corrosive environments.

[0007] Patent Document 4 discloses a high-strength steel plate with a strength of 1180 MPa or higher exhibiting excellent resistance to delayed fracture, corrosion resistance, and weldability under corrosive environments, as well as a method for manufacturing the same. However, the technology described in Patent Document 4 does not consider a high-strength steel plate with excellent yield ratio, ductility, and fatigue resistance at the shear end face.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent No. 7323093

[0011] Patent Document 2: Japanese Patent No. 7298647

[0012] Patent Document 3: Japanese Patent No. 6928112

[0013] Patent Document 4: Japanese Patent No. 6638694

[0014] Non-patent literature

[0015] Non-patent literature 1: Journal of the Intelligent Processing Society, 2013, Vol. 2, No. 3, pp. 110-118 Summary of the Invention

[0016] The present invention was developed in view of the above circumstances, and its purpose is to provide a steel plate, component and manufacturing method thereof with a tensile strength TS of 1180 MPa or more, a yield ratio YR of 65% or more, and excellent ductility, fatigue resistance of shear end face and resistance to delayed fracture in corrosive environment.

[0017] Here, the tensile strength TS (hereinafter also abbreviated as TS) and yield ratio YR (hereinafter also abbreviated as YR) can be determined according to JISZ 2241 (2022).

[0018] Excellent ductility means that the TS×El calculated according to the method of JIS Z 2241 (2022) is 14000 MPa·% or higher.

[0019] Excellent fatigue resistance of the shear end face means that the fatigue strength ratio of the shear end face (= fatigue limit of the shear end face / TS) determined by the full alternating bending test according to JIS Z 2275 (1978) is 0.25 or higher.

[0020] Excellent resistance to delayed fracture in corrosive environments means that, in the specific corrosive environment described in this invention, the resistance to delayed fracture is excellent, that is, the crack days are more than 63 days in the evaluation of metallic materials.

[0021] In order to achieve the above-mentioned objectives, the inventors conducted repeated and in-depth research and discovered the following results.

[0022] (1) By making the tempered martensite content above 83%, a TS of above 1180MPa can be achieved.

[0023] (2) Excellent ductility can be achieved by making the total amount of ferrite and bainite ferrite more than 5%.

[0024] (3) By making the amount of residual austenite less than 3% and the total amount of ferrite and bainite ferrite less than 15%, it is possible to achieve a YR of more than 65%.

[0025] (4) By making P(C) less than 70% and {P(S) - P(C)} less than 20%, excellent fatigue resistance of the shear end face and resistance to delayed fracture in corrosive environments can be achieved.

[0026] This invention is based on the above-mentioned insights. Specifically, the main structure of this invention is as follows.

[0027] [1] A steel plate having the following composition: by mass % containing C: 0.030% to 0.500%, Si: 0.010% to 2.500%, Mn: 0.10% to 5.00%, P: less than 0.100%, S: less than 0.0200%, Al: less than 1.000%, N: less than 0.0100%, and O: less than 0.0100%, with the remainder consisting of Fe and unavoidable impurities.

[0028] The steel plate has the following microstructure at 1 / 4 of its thickness: tempered martensite with an area fraction of 83% or more, retained austenite with a volume fraction of less than 3%, and a combined area fraction of ferrite and bainitic ferrite of 5% or more and less than 15%.

[0029] The following equations (1) and (2) are satisfied.

[0030] P(C)≤70%···(1)

[0031] {P(S)-P(C)}≤20%···(2)

[0032] In the formula,

[0033] P(S): The average occupancy of lath bundles with the maximum occupancy within the original austenite grains at a depth of 100 μm from the surface of the steel plate.

[0034] P(C): The average occupancy of lath bundles with the maximum occupancy within the original austenite grains at the center of the steel plate thickness.

[0035] [2] The steel plate according to [1] above, wherein the composition, by mass%, further contains at least one element selected from Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Ni: 1.00% or less, Co: 0.010% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less, Bi: 0.200% or less.

[0036] [3] The steel plate according to [1] or [2] above, wherein the steel plate has a coating on its surface.

[0037] [4] The steel plate according to any one of [1] to [3] above, wherein the crack days in the evaluation of the metallic material are 63 days or more.

[0038] [5] A component is made of steel plate as described in any one of [1] to [4] above.

[0039] [6] A method for manufacturing a steel plate, comprising hot rolling, pickling and cold rolling of steel having the composition described in [1] or [2] above to produce a cold-rolled plate,

[0040] The cold-rolled sheet is subjected to the following annealing process.

[0041] Heating is performed at an annealing temperature T1 of 750℃~850℃ and a holding time t1 of 10 seconds~1000 seconds.

[0042] Cooling with an average cooling rate CR1 of less than 5℃ / s from 700 to 600℃, cooling with an average cooling rate CR2 of 5℃ / s to 30℃ / s from a quenching start temperature T2 of (Ms+100℃) to (Ms-50℃) or higher but less than (Ms+50℃), and cooling using water quenching with an average cooling rate CR3 of 300℃ / s or higher from the quenching start temperature T2 to 80℃.

[0043] Heating is performed under the following conditions: tempering temperature T3 is 100℃~400℃ and holding time t3 at tempering temperature T3 is 10 seconds~10000 seconds.

[0044] In the water quenching cooling of the annealing process, two rollers that clamp the steel plate apply pressure from the surface and back of the steel plate. The pressure is applied under the condition that the distance between the rollers in the steel plate conveying direction is 20mm to 250mm and the pressure is 196N or more.

[0045] [7] In the steel plate manufacturing method described in [6] above, a plating treatment is performed.

[0046] [8] A method for manufacturing a component, comprising a step of performing at least one of forming and joining processes on the steel plate described in any one of [1] to [4] above to manufacture the component.

[0047] According to the present invention, steel sheets with a strength (TS) of 1180 MPa or higher, a yield (YR) of 65% or higher, and excellent ductility, fatigue resistance at the shear end face, and resistance to delayed fracture in corrosive environments can be obtained. Furthermore, by applying the steel sheets of the present invention to, for example, automotive structural components, improved fuel efficiency resulting from vehicle body lightweighting can be achieved. Therefore, it has significant industrial application value. Attached Figure Description

[0048] Figure 1 This is a schematic diagram illustrating lath bundles that have the maximum occupancy within the original austenite grains.

[0049] Figure 2 This is a schematic diagram illustrating the evaluation method (HeTsAce) for the delayed fracture characteristics of metallic materials.

[0050] Figure 3 This is an example of an image schematically showing the distribution of liquid droplets on the evaluation surface of a metallic material.

[0051] Figure 4 This is a schematic diagram illustrating the case where a shielding material is placed between the spray nozzle and the metal material in the evaluation method of delayed fracture characteristics of metallic materials.

[0052] Figure 5 This diagram schematically illustrates the state of the sprayed liquid in the atmosphere re-attaching to the evaluation surface when the distance between the shielding material and the evaluation surface of the metal material is changed.

[0053] Figure 6 This diagram illustrates one implementation of a corrosion test cycle for evaluating the delayed fracture characteristics of metallic materials.

[0054] Figure 7 This figure illustrates another implementation of a corrosion test cycle for evaluating the delayed fracture characteristics of metallic materials.

[0055] Figure 8This is a diagram schematically illustrating a test piece used to evaluate the delayed fracture characteristics in the embodiments.

[0056] Figure 9 This is a schematic diagram illustrating the pressurization method during water cooling in the steel plate manufacturing method of the present invention. Detailed Implementation

[0057] The embodiments of the present invention will be described below.

[0058] [Steel plate]

[0059] The steel plate of the present invention has the following composition: by mass % C: 0.030% to 0.500%, Si: 0.010% to 2.500%, Mn: 0.10% to 5.00%, P: less than 0.100%, S: less than 0.0200%, Al: less than 1.000%, N: less than 0.0100%, and O: less than 0.0100%, with the remainder consisting of Fe and unavoidable impurities.

[0060] The aforementioned steel plate has the following microstructure at the 1 / 4 position of its thickness: the area fraction of tempered martensite is 83% or more, the area fraction of retained austenite is less than 3%, and the combined area fraction of ferrite and bainitic ferrite is 5% or more and less than 15%.

[0061] The following equations (1) and (2) are satisfied.

[0062] P(C)≤70%···(1)

[0063] {P(S)-P(C)}≤20%···(2)

[0064] In the formula,

[0065] P(S): The average occupancy of lath bundles with the maximum occupancy within the original austenite grains at a depth of 100 μm from the surface of the steel plate.

[0066] P(C): The average occupancy of lath bundles with the maximum occupancy within the original austenite grains at the center of the steel plate thickness.

[0067] First, the appropriate range of the steel plate's composition and the rationale for limiting it will be explained. It should be noted that, in the following explanation, unless otherwise specified, the "%" indicating the content of the steel's constituent elements refers to "mass %".

[0068] C: 0.030%~0.500%

[0069] Carbon (C) is one of the essential components of steel, and especially in this invention, it is a crucial element affecting the area fraction (hereinafter also referred to as fraction) of tempered martensite and the fatigue resistance of the shear end face. If the C content is less than 0.030%, the fraction of tempered martensite decreases, making it difficult to achieve a TS (temperature resistance) of over 1180 MPa.

[0070] On the other hand, if the C content exceeds 0.500%, the tempered martensite becomes embrittled, making it difficult to obtain excellent fatigue resistance properties at the shear end face.

[0071] Therefore, the C content is 0.030% to 0.500%. The C content is preferably 0.050% or more. The C content is more preferably 0.100% or more. Furthermore, the C content is preferably 0.400% or less. The C content is more preferably 0.350% or less.

[0072] Si: 0.010%~2.500%

[0073] Si is one of the essential components of steel, especially in this invention, where it plays a crucial role in influencing the amount of retained austenite due to its ability to inhibit carbide formation and promote the formation of retained austenite during continuous annealing. If the Si content is less than 0.010%, it is difficult to achieve a steel strength (TS) of over 1180 MPa.

[0074] On the other hand, if the Si content exceeds 2.500%, the residual austenite increases excessively, making it difficult to achieve YR≥65%.

[0075] Therefore, the Si content is 0.010% to 2.500%. The Si content is preferably 0.050% or more. The Si content is more preferably 0.100% or more. Furthermore, the Si content is preferably 2.000% or less. The Si content is more preferably 1.200% or less. The Si content is more preferably 0.500% or less, and even more preferably 0.300% or less.

[0076] Mn: 0.10%~5.00%

[0077] Mn is one of the essential components of steel, and especially in this invention, it is a crucial element that influences the tempered martensite content and the resistance to delayed fracture in corrosive environments. If the Mn content is less than 0.10%, the tempered martensite content decreases, making it difficult to achieve a temper strength (TS) of over 1180 MPa.

[0078] On the other hand, if the Mn content exceeds 5.00%, it promotes corrosion of the steel plate and the generation of hydrogen associated with corrosion, making it difficult to achieve excellent resistance to delayed fracture in corrosive environments. Therefore, the Mn content is 0.10% to 5.00%. The Mn content is preferably 0.50% or more. The Mn content is more preferably 0.80% or more. The Mn content is preferably 4.50% or less. The Mn content is more preferably 4.00% or less.

[0079] P: below 0.100%

[0080] Phosphorus segregation at the original austenite grain boundaries causes grain boundary embrittlement. Therefore, if the phosphorus content exceeds 0.100%, the ultimate deformation capacity of the steel plate will be reduced, making it difficult to achieve excellent fatigue resistance at the shear end face. Therefore, the phosphorus content needs to be set to 0.100% or less. The phosphorus content is preferably 0.070% or less. More preferably, it is 0.050% or less, and even more preferably 0.020% or less.

[0081] It should be noted that there is no specific lower limit for the content of phosphorus (P), but P is a solid solution strengthening element that can improve the strength of steel plates, so it is preferably 0.001% or more. The content of P is more preferably 0.002% or more.

[0082] S: Below 0.0200%

[0083] Sulfide (S) exists in the form of sulfides. If the S content exceeds 0.0200%, it will reduce the ultimate deformation capacity of the steel plate, making it difficult to achieve excellent fatigue resistance at the shear end face. Therefore, the S content needs to be set to 0.0200% or less. The S content is preferably 0.0050% or less. More preferably, the S content is 0.0030% or less, and even more preferably 0.0020% or less.

[0084] It should be noted that there is no specific lower limit for the content of sulfur (S). From the perspective of production technology constraints, the content of S is preferably 0.0001% or more. More preferably, the content of S is 0.0002% or more.

[0085] Al: Below 1.000%

[0086] Al exists in the form of oxides. If the Al content exceeds 1.000%, it will reduce the ultimate deformation capacity of the steel plate, making it difficult to achieve excellent fatigue resistance at the shear end face. Therefore, the Al content needs to be set to 1.000% or less. The Al content is preferably 0.500% or less. More preferably, it is 0.200% or less, and even more preferably 0.100% or less.

[0087] It should be noted that there is no specific lower limit for the Al content. From the perspective of production technology constraints, the Al content is preferably 0.001% or more. The Al content is more preferably 0.002% or more. The Al content is more preferably 0.005% or more, and even more preferably 0.010% or more.

[0088] N: below 0.0100%

[0089] Nitrogen (N) exists in the form of nitrides. If the N content exceeds 0.0100%, it will reduce the ultimate deformation capacity of the steel plate, making it difficult to achieve excellent fatigue resistance at the shear end face. Therefore, the N content needs to be set to 0.0100% or less. Preferably, the N content is 0.0050% or less.

[0090] It should be noted that there is no specific lower limit for the N content. From the perspective of production technology constraints, the N content is preferably 0.0001% or more. More preferably, the N content is 0.0010% or more, and even more preferably 0.0020% or more.

[0091] O: Below 0.0100%

[0092] O exists in the form of oxides. If the O content exceeds 0.0100%, it will reduce the ultimate deformation capacity of the steel plate, making it difficult to achieve excellent fatigue resistance at the shear end face. Therefore, the O content needs to be set to 0.0100% or less. Preferably, the O content is 0.0050% or less.

[0093] It should be noted that there is no specific lower limit for the content of oxygen (O). From the perspective of production technology constraints, the content of O is preferably 0.0001% or more. More preferably, the content of O is 0.0010% or more, and even more preferably 0.0015% or more.

[0094] One embodiment of the high-strength steel sheet of the present invention has a composition containing the above-described components, with the remainder consisting of Fe and unavoidable impurities. Examples of unavoidable impurities include Zn, Pb, As, Ge, Sr, and Cs. A total content of 0.100% or less of these impurities is permissible. It should be noted that the steel sheet of one embodiment of the present invention preferably has a composition containing the above-described components, with the remainder consisting of Fe and unavoidable impurities.

[0095] In addition to the above-mentioned composition, the steel plate of the present invention may also contain, by mass percent, at least one element selected from Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Ni: 1.00% or less, Co: 0.010% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less, and Bi: 0.200% or less.

[0096] Ti: below 0.200%, Nb: below 0.200%, V: below 0.200%

[0097] If the contents of Ti, Nb, and V are all below 0.200%, large coarse precipitates or inclusions will not be generated, and the ultimate deformation capacity of the steel plate will not be reduced. Therefore, the excellent fatigue resistance of the shear end face will not be reduced. Thus, when containing at least any one of Ti, Nb, and V, the contents of each of Ti, Nb, and V are set to 0.200% or less. Preferably, these contents are each below 0.100%.

[0098] It should be noted that there are no specific lower limits for the content of Ti, Nb, and V. By forming fine carbides, nitrides, or carbonitrides during hot rolling or continuous annealing, the strength of the steel sheet can be improved. Therefore, the content of Ti, Nb, and V is preferably 0.001% or more. These contents are more preferably 0.002% or more, and even more preferably 0.003% or more.

[0099] Ta: below 0.10%, W: below 0.10%

[0100] If Ta and W are both below 0.10%, large coarse precipitates or inclusions will not be generated, the ultimate deformation capacity of the steel plate will not be reduced, and therefore the fatigue resistance of the shear end face will not be reduced. Therefore, when containing at least one of Ta and W, the content of Ta and W is each set to below 0.10%. Preferably, these contents are below 0.08%.

[0101] It should be noted that there is no specific lower limit for the content of Ta and W. The strength of the steel plate can be improved by forming fine carbides, nitrides or carbonitrides during hot rolling or continuous annealing. Therefore, the content of Ta and W is preferably 0.01% or more.

[0102] These contents are more preferably 0.02% or more, and even more preferably 0.03% or more.

[0103] B: Below 0.0100%

[0104] If B is below 0.0100%, cracks will not form inside the steel plate during casting or hot rolling, and the ultimate deformation capacity of the steel plate will not be reduced. Therefore, the fatigue resistance of the shear end face will not be reduced. Thus, when B is present, the B content is set to 0.0100% or less. Preferably, the B content is 0.0080% or less.

[0105] It should be noted that there is no specific lower limit for the content of B. B is an element that segregates at the austenite grain boundaries during annealing and improves hardenability. Therefore, the content of B is more preferably 0.0003% or more.

[0106] Cr: less than 1.00%, Mo: less than 1.00%, Ni: less than 1.00%

[0107] If Cr, Mo, and Ni are each 1.00% or less, coarse precipitates or inclusions will not increase, the ultimate deformation capacity of the steel plate will not decrease, and therefore the fatigue resistance of the shear end face will not decrease. Therefore, when containing at least one of Cr, Mo, and Ni, the content of each Cr, Mo, and Ni is set to 1.00% or less. Preferably, these contents are 0.80% or less. More preferably, these contents are 0.75% or less, and even more preferably, 0.70% or less.

[0108] It should be noted that there is no specific lower limit for the content of Cr, Mo, and Ni. Since they are elements that improve hardenability, the content of Cr, Mo, and Ni is preferably 0.01% or more. These contents are more preferably 0.02% or more.

[0109] Co: less than 0.010%

[0110] If the Co content is below 0.010%, it will not increase the amount of coarse precipitates or inclusions, nor will it reduce the ultimate deformation capacity of the steel plate, thus the fatigue resistance of the shear end face will not decrease. Therefore, when Co is present, the Co content is set to below 0.010%. The Co content is preferably below 0.008%. The Co content is more preferably below 0.007%.

[0111] It should be noted that there is no specific lower limit for the content of Co. Since it is an element that improves hardenability, the content of Co is preferably 0.001% or more.

[0112] Cu: below 1.00%

[0113] If the Cu content is 1.00% or less, it will not increase the amount of coarse precipitates or inclusions, nor will it reduce the ultimate deformation capacity of the steel plate. Therefore, the fatigue resistance of the shear end face will not decrease. Thus, when Cu is present, the Cu content is set to 1.00% or less. The Cu content is preferably 0.80% or less.

[0114] It should be noted that there is no specific lower limit for the Cu content. Since it is an element that improves hardenability, the Cu content is preferably 0.01% or higher.

[0115] Sn: below 0.200%

[0116] If the Sn content is below 0.200%, cracks will not form inside the steel plate during casting or hot rolling, and the ultimate deformation capacity of the steel plate will not be reduced. Therefore, the fatigue resistance of the shear end face will not be reduced. Thus, when Sn is present, the Sn content is set to below 0.200%. The Sn content is preferably below 0.150%.

[0117] It should be noted that there is no specific lower limit for the Sn content. Since Sn is an element that improves hardenability (and usually an element that improves corrosion resistance), the Sn content is more preferably 0.001% or more. The Sn content is more preferably 0.002% or more.

[0118] Sb: below 0.200%

[0119] If the Sb content is 0.200% or less, it will not increase the amount of coarse precipitates or inclusions, nor will it reduce the ultimate deformation capacity of the steel plate. Therefore, the fatigue resistance of the shear end face will not decrease. Thus, when Sb is present, the Sb content is set to 0.200% or less. The Sb content is preferably 0.150% or less. More preferably, the Sb content is 0.100% or less.

[0120] It should be noted that there is no specific lower limit for the Sb content. Since it is an element that controls the surface softening thickness and can adjust the strength, the Sb content is preferably 0.001% or more. The Sb content is more preferably 0.002% or more.

[0121] Ca: less than 0.0100%, Mg: less than 0.0100%, REM: less than 0.0100%

[0122] If the contents of Ca, Mg, and REM are all below 0.0100%, coarse precipitates or inclusions will not increase, the ultimate deformation capacity of the steel plate will not decrease, and therefore the fatigue resistance of the shear end face will not be reduced. Therefore, when at least one of Ca, Mg, and REM is present, the contents of Ca, Mg, and REM are preferably set to 0.0100% or less. Preferably, these contents are 0.0050% or less.

[0123] It should be noted that there is no specific lower limit for the content of Ca, Mg and REM. Since they are elements that make the shape of nitrides or sulfides spherical and improve the ultimate deformation capacity of steel plates, the content of Ca, Mg and REM is preferably 0.0001% or more.

[0124] These contents are more preferably 0.0002% or more, and even more preferably 0.0005% or more.

[0125] Zr: below 0.100%, Te: below 0.100%

[0126] If Zr and Te are both 0.100% or less, coarse precipitates or inclusions will not increase, the ultimate deformation capacity of the steel plate will not decrease, and therefore the fatigue resistance of the shear end face will not be reduced. Therefore, when containing at least one of Zr and Te, the content of Zr and Te is set to 0.100% or less. Preferably, these contents are 0.095% or less. More preferably, these contents are 0.090% or less, and even more preferably, 0.085% or less.

[0127] It should be noted that there is no specific lower limit for the content of Zr and Te. Since they are elements that spheroidize the shape of nitrides or sulfides and improve the ultimate deformation capacity of steel plates, the content of Zr and Te is preferably 0.001% or more. These contents are more preferably 0.002% or more.

[0128] Hf: below 0.10%

[0129] If Hf is 0.10% or less, it will not increase coarse precipitates or inclusions, nor will it reduce the ultimate deformation capacity of the steel plate, thus the fatigue resistance of the shear end face will not decrease. Therefore, when Hf is present, the Hf content is set to 0.10% or less. The Hf content is preferably 0.09% or less. The Hf content is more preferably 0.08% or less, and even more preferably 0.07% or less.

[0130] It should be noted that there is no specific lower limit for the content of Hf. Since it is an element that makes nitrides or sulfides spherical and improves the ultimate deformation capacity of steel plates, the content of Hf is preferably 0.001% or more, and more preferably 0.010% or more.

[0131] Bi: below 0.200%

[0132] If the Bi content is below 0.200%, it will not increase the amount of coarse precipitates or inclusions, nor will it reduce the ultimate deformation capacity of the steel plate; therefore, the fatigue resistance of the shear end face will not decrease. Thus, when Bi is present, the Bi content is set to 0.200% or less. The preferred Bi content is 0.190% or less.

[0133] It should be noted that there is no specific lower limit for the Bi content. Since it is an element that reduces segregation, the Bi content is preferably 0.001% or more. More preferably, the Bi content is 0.002% or more, and even more preferably 0.003% or more.

[0134] It should be noted that when the contents of Ti, Nb, V, Ta, W, B, Cr, Mo, Ni, Co, Cu, Sn, Sb, Ca, Mg, REM, Zr, Te, Hf and Bi are all less than the preferred lower limit, the effect of the present invention will not be impaired, and therefore they are contained as unavoidable impurities.

[0135] Next, the steel structure of the steel plate of the present invention will be described.

[0136] Tempered martensite: ≥83% by area fraction

[0137] This is one of the important inventive elements in this invention. By making tempered martensite the main phase, a strength (TS) of 1180 MPa or higher can be achieved. To obtain this effect, the tempered martensite needs to have an area fraction of 83% or higher. Therefore, the tempered martensite has an area fraction of 83% or higher. Preferably, the area fraction of the tempered martensite is 84% ​​or higher.

[0138] There is no particular upper limit, but the area fraction of tempered martensite is preferably 95% or less, and more preferably 94% or less.

[0139] Here, the method for determining the area fraction of tempered martensite is as follows. After grinding the L-section of the steel plate, it is etched with a 1 vol.% nitric acid ethanol solution. At 1 / 4 of the plate thickness (a position corresponding to 1 / 4 of the plate thickness in the depth direction from the surface of the steel plate), 10 fields of view are observed using SEM at a magnification of 2000x with a field of view of 30 μm × 30 μm.

[0140] It should be noted that in the above microstructure images, tempered martensite is a microstructure with fine internal irregularities and containing carbides. The area fraction of tempered martensite can be calculated based on the average of these values.

[0141] Retained austenite: less than 3% by volume fraction

[0142] In this invention, this is one of the important inventive elements. When the retained austenite volume fraction is 3% or more, it is difficult to achieve YR ≥ 65%. The reason it is difficult to achieve YR ≥ 65% is that during the tensile test, the retained austenite transforms into martensite, resulting in a decrease in YS. Therefore, the volume fraction of retained austenite is less than 3%. Preferably, the volume fraction of retained austenite is 1% or less. It should be noted that the lower limit of the volume fraction of retained austenite is not particularly limited and can be 0%.

[0143] Here, the method for determining the volume fraction of retained austenite is as follows. For retained austenite, the steel plate is ground to 1 / 4 of its thickness, and then further ground to 0.1 mm using chemical grinding. Using an X-ray diffraction apparatus, the integral intensity ratios of the diffraction peaks on the {200}, {220}, and {311} planes of fcc iron and the {200}, {211}, and {220} planes of bcc iron are measured using CoKα rays. The obtained nine integral intensity ratios are then averaged to obtain the final austenite.

[0144] The total amount of ferrite and bainitic ferrite: 5% or more but less than 15% by area fraction.

[0145] In this invention, this is one of the important inventive elements. When the combined area fraction of ferrite and bainitic ferrite is 15% or more, it is difficult to achieve YR≥65%.

[0146] On the other hand, if the combined area fraction of ferrite and bainitic ferrite is less than 5%, it is difficult to achieve excellent ductility. Therefore, the combined area fraction of ferrite and bainitic ferrite is 5% or more and less than 15%. Their combined area fraction is preferably 6% or more. Their combined area fraction is preferably 13% or less.

[0147] Here, the method for determining the total area fraction of ferrite and bainitic ferrite is as follows. After grinding the L-section of the steel plate, it was etched with a 1 vol.% nitric acid-ethanol solution. At 1 / 4 of the plate thickness (a position corresponding to 1 / 4 of the plate thickness in the depth direction from the steel plate surface), 10 fields of view were observed using SEM at 2000x magnification with a field of view of 30 μm × 30 μm. It should be noted that in the above microstructure images, the ferrite and bainitic ferrite are concave structures with flat interiors, and are structures without internal carbides. The total area fraction of ferrite and bainitic ferrite can be calculated based on the average of these values.

[0148] Residual structures other than those mentioned above can be considered, such as pearlite, fresh martensite, and acicular ferrite. These residual structures, if their area fraction is less than 5%, will not affect the properties and are therefore permissible.

[0149] P(C)≤70%···(1)

[0150] P(C): The average occupancy of lath bundles with the maximum occupancy within the original austenite grains at the center of the steel plate thickness.

[0151] In this invention, this is one of the important inventive elements. The occupancy of lath bundles with the maximum occupancy within the original austenite grains at the center of the steel plate thickness affects the fatigue resistance of the shear end face and the resistance to delayed fracture in corrosive environments. Lath bundles with the maximum occupancy within the original austenite grains refer to, for example... Figure 1 As shown, within the original austenite grain, there are a maximum of four regions with the same crystal inertial plane during the phase transformation, referred to as lath bundles, among which the lath bundle with the largest occupancy is the one with the largest occupancy. The occupancy of a lath bundle within the original austenite grain is determined by dividing the area of ​​the specified lath bundle by the total area within the original austenite grain.

[0152] The inventors have conducted repeated and in-depth research and found that by reducing the occupancy rate of lath bundles with the maximum occupancy rate within the original austenite grains at the center of the steel plate thickness, specifically by making the average occupancy rate of lath bundles with the maximum occupancy rate within the original austenite grains at the center of the steel plate thickness below 70%, the microstructure is refined, crack propagation can be suppressed, thus improving the fatigue resistance of the shear end face and the resistance to delayed fracture in corrosive environments.

[0153] Therefore, the average value P(C) of the occupancy of the lath bundles with the maximum occupancy within the original austenite grains at the center of the steel plate thickness is set to 70% or less. Preferably, the average value P(C) of this occupancy is 60% or less.

[0154] It should be noted that there is no particular limitation on the lower limit of the average occupancy of lath bundles having the maximum occupancy within the original austenite grains. There can be a maximum of four types of lath bundles, and when all four types of lath bundles exist equally, the occupancy of the lath bundles having the maximum occupancy within the original austenite grains is 25%. Therefore, the average occupancy P(C) of the lath bundles having the maximum occupancy within the original austenite grains at the center of the steel plate thickness is preferably 25% or more, but is not limited to this.

[0155] {P(S)-P(C)}≤20%···(2)

[0156] P(S): The average occupancy of lath bundles with the maximum occupancy within the original austenite grains at a depth of 100 μm from the surface of the steel plate.

[0157] P(C): The average occupancy of lath bundles with the maximum occupancy within the original austenite grains at the center of the steel plate thickness.

[0158] In this invention, this is one of the important inventive elements. The difference between P(S) and P(C) affects the fatigue resistance of the shear end face and the resistance to delayed fracture in corrosive environments. If {P(S) - P(C)} ≤ 20%, it means that the occupancy rate of the lath bundles in the surface portion of the steel plate is too large compared to the occupancy rate of the lath bundles in the center portion of the steel plate, which will promote the formation of fatigue-induced cracks and delayed fracture-induced cracks in the surface portion of the steel plate. Therefore, {P(S) - P(C)} is 20% or less. Preferably, {P(S) - P(C)} is 15% or less.

[0159] Here, the method for determining the average occupancy of lath bundles with the maximum occupancy within the original austenite grains is as follows. First, a test piece for microstructure observation is taken from the steel plate. Next, the taken test piece is ground using colloidal silica vibratory grinding with the rolling direction section (L section) as the observation surface. The observation surface is mirror-like. Next, electron backscatter diffraction (EBSD) measurements are performed at a depth of 100 μm from the surface of the steel plate and at the center of the plate thickness to obtain local crystal orientation data. At this time, the SEM magnification is 1000x, the step size is 0.2 μm, the measurement area is 80 μm square, and the WD is 15 mm. The obtained local orientation data is analyzed using OIMAnalysis7 (OIM), and a color-coded diagram (CP diagram) is created for each Close-packed Planegroup (CP group) using the method described in Non-Patent Literature 1 (Journal of Intelligent Process Engineering, 2013, Vol. 2, No. 3, pp. 110-118). In this invention, lath bundles are defined as regions belonging to the same CP group. The area of ​​the lath bundle with the maximum occupancy is calculated from the obtained CP diagram, and then divided by the total area within the original austenite grain to determine the occupancy of the lath bundle with the maximum occupancy within the original austenite grain. This analysis is performed on 10 or more adjacent original austenite grains, and their average value is taken as the average occupancy of the lath bundle with the maximum occupancy within the original austenite grain.

[0160] The steel sheet of the present invention may have a coating on its surface. Examples of coatings include hot-dip galvanized coatings, alloyed hot-dip galvanized coatings, and electroplated zinc coatings. Examples of coatings other than zinc coatings include aluminum coatings and alloy coatings. Examples of alloy coatings include hot-dip galvanized-aluminum-magnesium alloy coatings and electroplated Zn-Ni alloy coatings.

[0161] The thickness of the steel plate of the present invention is preferably 0.5 mm or more. Furthermore, the thickness is preferably 3.0 mm or less.

[0162] In the evaluation method for delayed fracture characteristics of metallic materials (HeTsAce), a crack duration of 63 days or more is considered acceptable.

[0163] In the evaluation method of delayed fracture characteristics of steel plates under corrosive environments (HeTsAce) of metallic materials according to the present invention, it can be judged that the steel plates have excellent resistance to delayed fracture under corrosive environments.

[0164] Specifically, the steel plate of the present invention has a cracking time of 63 days or more in the following evaluation method for delayed fracture characteristics of metallic materials (HeTsAce).

[0165] (HeTsAce)

[0166] In the evaluation method of delayed fracture characteristics of metallic materials, a process consisting of at least one chloride adhesion process (A) and an etching process (B) is performed.

[0167] In the chloride adsorption process (A), droplets of an aqueous solution containing chloride are adsorbed at a chloride adsorption amount of 1000–20000 mg / m³. 2 The method of attaching it to the evaluation surface of the metallic material being evaluated;

[0168] In the etching process (B), the process is carried out more than once in an atmosphere at a temperature Tb1 below 60°C and within a certain range, with the following cycle consisting of the drying process (b1), the wetting process (b2), the transition process (b3), and the transition process (b4) as one cycle.

[0169] At least in the initial chloride adhesion process (A), the distribution of the droplets of the above-mentioned chloride-containing aqueous solution on the evaluation surface of the above-mentioned metal material is as follows:

[0170] The average contact area of ​​the droplets on the evaluation surface of the aforementioned metallic material is 0.1 mm. 2 Above and below 3.0mm 2 The total contact area of ​​the aforementioned droplets relative to the area of ​​the evaluation surface of the aforementioned metal material is 40% to 80%, and the standard deviation of the contact area of ​​the aforementioned droplets on the evaluation surface of the aforementioned metal material is 3.0 mm. 2 the following.

[0171] Drying process (b1): A process of drying metal materials in an atmosphere with a relative humidity of less than 45% (Hb1) for 1.0 to 5.0 hours.

[0172] Wetting process (b2): A process of wetting metal materials for 1.0 to 5.0 hours in an atmosphere with a relative humidity of 80% or higher (Hb2).

[0173] Transition process (b3): ​​A process of transitioning from the atmosphere with relative humidity Hb1 to the atmosphere with relative humidity Hb2 at a relative humidity change rate of 30% / h or less.

[0174] Transition process (b4): A process of transitioning from the atmosphere with relative humidity Hb2 to the atmosphere with relative humidity Hb1 at a relative humidity change rate of 30% / h or less.

[0175] In this invention, the metal material taken from a steel plate is used as the evaluation object. The method for taking the metal material from the steel plate is not particularly limited. For example, the metal material can be taken by cutting the steel plate to a specified size. In HeTsAce, it is preferable to apply stress to the metal material being evaluated. As a method for applying stress to the metal material, methods of processing the metal material can be cited. Examples of such processing methods include bending, bulging, stretching, and torsion. In addition, methods such as using bolts to fix the material in a stress-inducing shape, or utilizing residual stress remaining after processing, can also be cited. In the evaluation method of this invention, the metal material subjected to stress as described above can be subjected to at least one (or two) steps including a chloride adhesion process (A) and a corrosion process (B). Furthermore, in the evaluation method of this invention, after performing at least one step including a chloride adhesion process (A) and a corrosion process (B), the state of the metal material is checked, and the delayed fracture characteristics of the metal material can be evaluated based on the checked state of the metal material. The above confirmation can be made, for example, by visually observing whether there are cracks in the metal material and the extent of those cracks.

[0176] In this invention, to evaluate the delayed fracture characteristics of a metallic material, a chloride adhesion process (A) and an etching process (B) are performed while the metallic material is under stress. Then, after performing these processes more than once, the delayed fracture characteristics are evaluated by confirming the presence and extent of cracks in the metallic material.

[0177] (Chloride adhesion process (A))

[0178] Chloride adsorption process (A) involves applying droplets of an aqueous solution containing chloride at a chloride adsorption amount of 1000–20000 mg / m³. 2 The process involves attaching the chloride-containing aqueous solution to the evaluation surface of the metal material in a specific manner. Furthermore, in the evaluation method of the present invention, the distribution of droplets (droplet attachment distribution) of the chloride-containing aqueous solution on the evaluation surface of the metal material in at least the initial (first) chloride attachment step (A) satisfies the following condition: the average contact area of ​​the droplets on the evaluation surface of the metal material is 0.1 mm. 2 Above and below 3.0mm 2The total contact area of ​​the droplets relative to the area of ​​the evaluation surface of the metal material is 40%–80%, and the standard deviation of the contact area of ​​the droplets on the evaluation surface of the metal material is 3.0 mm. 2 the following.

[0179] Chloride adhesion amount: 1000~20000 mg / m³ 2 >

[0180] The amount of chloride adhering to metallic materials (excluding the solid component of chloride excluding solvents such as water) is 1000–20000 mg / m³. 2 The above-mentioned adhesion amount corresponds to the hypothetical chloride adhesion amount in the actual atmospheric corrosive environment of a vehicle in motion. When the above-mentioned adhesion amount is less than 1000 mg / m³... 2 In corrosive environments, corrosion progresses very little, resulting in minimal hydrogen generation and intrusion into the metallic material, making delayed fracture unlikely. On the other hand, if the aforementioned adhesion amount exceeds 20,000 mg / m³... 2 This would deviate significantly from actual corrosion conditions, becoming an excessive durability test, and therefore not meeting the intended purpose. Therefore, the aforementioned adhesion amount of 20000 mg / m² is appropriate. 2 The following is based on the viewpoint of simulating the corrosion morphology in the actual atmospheric corrosion environment of automobile driving and promoting corrosion. Therefore, the aforementioned adhesion amount is preferably greater than 5000 mg / m³. 2 Furthermore, based on the above viewpoint, the preferred adhesion amount is 12000 mg / m³. 2 the following.

[0181] It should be noted that the amount of chloride adhering can be calculated by multiplying the mass difference of the test subject (metal material) before and after the chloride-containing aqueous solution adhering in the chloride adhering process (A) by the chloride concentration of the chloride-containing aqueous solution, and then dividing by the evaluation surface area of ​​the test subject. It should also be noted that when measuring the mass difference, if the chloride-containing aqueous solution adheres to areas outside the evaluation surface of the test subject, appropriate measures can be taken such as masking the areas outside the evaluation surface or wiping away the chloride-containing aqueous solution adhering to those areas. Furthermore, to change the amount of chloride adhering, the amount of chloride-containing aqueous solution adhering to the metal material can be controlled, for example, by changing the chloride concentration of the chloride-containing aqueous solution or by changing the time the chloride-containing aqueous solution is applied (the process time of the chloride adhering process (A)).

[0182] In the chloride adhesion process (A), chloride is adhered to the metal material to obtain the desired amount of chloride adhesion. Preferably, the chloride contains one or more of the following: sodium (NaCl), potassium (KCl), calcium (CaCl2), and magnesium (MgCl2), which are present in the atmospheric environment commonly used with metal materials. It should be noted that in the chloride adhesion process (A), when adhering chloride to the metal material, a chloride-based component can also be adhered, containing both chloride and other components. Here, a chloride-based component refers to a component where chloride, converted from solid components, exceeds 50% by mass of all components. Components other than chloride include, but are not limited to, sulfides and nitrate compounds. Considering the actual atmospheric corrosion environment, it is preferable to adhere a NaCl-based component (where NaCl exceeds 50% by mass of all components) to the metal material.

[0183] Furthermore, when simulating the delayed fracture characteristics in areas where de-icing agents are frequently dispersed in winter, it is preferable that the chloride adhering to the metal material has a composition similar to that of the de-icing agents dispersed in that area. Examples of components with a composition similar to that of de-icing agents include components mainly composed of CaCl2 (CaCl2 constitutes more than 50% by mass of all components), components mainly composed of MgCl2 (MgCl2 constitutes more than 50% by mass of all components), and components mainly composed of NaCl (NaCl constitutes more than 50% by mass of all components).

[0184] Furthermore, as chlorides that adhere to metallic materials, compositions containing multiple metal salts can also be used. Examples of compositions containing multiple metal salts include the American Society of Automotive Technology (SAE J2334) (0.5% by mass NaCl – 0.1% by mass CaCl2 – 0.075% by mass NaHCO3), artificial seawater (2.5% by mass NaCl – 0.5% by mass MgCl2 – 0.12% by mass CaCl2 – 0.07% by mass KCl and others (e.g., an aqueous solution of Aquamarine (registered trademark) manufactured by Hachishu Pharmaceutical Co., Ltd.)).

[0185] The method for attaching chlorides to metallic materials (chloride attachment method) is not particularly limited as long as it achieves the desired distribution of chloride-containing aqueous solution droplets on the evaluation surface of the metallic material. Examples of chloride-containing aqueous solutions include those containing chlorides as the main component (usually aqueous solutions such as salt water, hereinafter also referred to as salt water). The following explanation uses salt water as an example of a chloride-containing aqueous solution.

[0186] One method for chloride adhesion is spraying. Within spraying, a method using a spray nozzle to adhere brine can be cited. Types of spray nozzles include single-fluid spray nozzles (nozzles that atomize and spray pressurized liquid) and two-fluid spray nozzles (nozzles that atomize liquid using high-speed fluids such as compressed air). Two-fluid spray nozzles can be further categorized into pressurized (liquid is supplied to the nozzle under pressure) and suction (liquid is drawn up and sprayed using the force of compressed air). From the perspective of uniform droplet adhesion distribution, spray nozzles are preferred. Furthermore, since brine is used, the material of the spray nozzle is preferably a corrosion-resistant metal such as stainless steel.

[0187] The chloride concentration in the brine is not particularly limited. However, when using a spray nozzle to control the droplet distribution of the brine, if a brine with a chloride concentration of less than 2.0% by mass is used to adhere the brine to the metal material, the spraying time becomes longer in order to obtain a suitable amount of chloride adhesion, making it difficult to achieve the desired droplet distribution on the evaluation surface of the metal material. Therefore, the chloride concentration in the brine is preferably 2.0% by mass or more, more preferably 5.0% by mass or more. On the other hand, when a brine with a chloride concentration exceeding 20% ​​by mass is used to adhere the brine to the metal material, chloride is easily precipitated in the spray nozzle, leading to nozzle clogging and making it difficult to spray brine droplets of a stable size, thus making it difficult to achieve the desired droplet distribution on the evaluation surface of the metal material. As a result, the amount of chloride adhesion on the evaluation surface of the metal material varies depending on the location, with localized corrosion occurring in areas with high chloride adhesion and increased hydrogen intrusion. Therefore, the delayed fracture characteristics change within the evaluation surface of the metal material, and the evaluation accuracy of the delayed fracture characteristics decreases. This trend becomes particularly significant when the amount of chloride adhesion is high. Therefore, the chloride concentration in the brine is preferably 20% by mass or less, and more preferably 15% by mass or less.

[0188] It should be noted that the chloride concentration in the brine is preferably adjusted according to the target chloride deposition amount. A low-concentration brine is preferred when the chloride deposition amount is low, while a high-concentration brine is preferred when the chloride deposition amount is high. To reduce chloride deposition on the evaluation surface of the metal material using a high-concentration brine, the total brine spray volume must be reduced, which easily leads to an excessively small average contact area of ​​the brine droplets adhering to the evaluation surface and a low average contact area ratio of the brine droplets relative to the total area of ​​the evaluation surface. Conversely, to increase chloride deposition on the evaluation surface of the metal material using a low-concentration brine, the total brine spray volume needs to be increased, which easily leads to an excessively large average contact area of ​​the brine droplets adhering to the evaluation surface and a high average contact area ratio of the brine droplets relative to the evaluation surface area.

[0189] [Distribution of droplets containing chloride-containing aqueous solution adhering to the evaluation surface of the metal material during the initial chloride adsorption process (A)]

[0190] In the evaluation method of the present invention, it is necessary to control the distribution of brine droplets on the evaluation surface of the metal material in at least the initial (i.e., at least the first implementation) chloride adhesion step (A) within the range described below. It is considered that in the first chloride adhesion step, the location of the brine on the evaluation surface of the metal material primarily becomes the corrosion initiation point of that evaluation surface. Furthermore, in the second chloride adhesion step, the brine spray occurs after the first chloride adhesion step, and corrosion products have formed on the evaluation surface. Even if the brine droplets are uniformly adhered to the evaluation surface of the metal material, wetting and spreading will occur due to the influence of the corrosion products. Therefore, it is important to uniformly control the distribution of brine droplets on the evaluation surface of the metal material in the first chloride adhesion step.

[0191] Figure 2 This is a schematic diagram illustrating an example of the evaluation method of the present invention. For example... Figure 2 As shown, in the evaluation method of the present invention, brine is sprayed from a spray nozzle, causing brine droplets to adhere to the evaluation surface of the metal material. At this time, in the initial chloride adhesion step (A), the distribution of brine droplets adhering to the evaluation surface of the metal material (droplet adhesion distribution) is controlled within a specified range.

[0192] Average contact area of ​​droplets on the evaluation surface of metallic materials: 0.1 mm 2 Above and below 3.0mm 2 >

[0193] In the evaluation method of the present invention, at least in the first chloride adhesion step (A), the average contact area of ​​the droplets on the evaluation surface of the metal material (average contact area per droplet) is 0.1 mm. 2 Above and below 3.0mm 2 The average contact area mentioned above is less than 0.1 mm. 2 At that time, due to the small size of the droplets, the amount of chloride adhering to the target concentration was insufficient. Therefore, the average contact area was 0.1 mm. 2 The above. The preferred average contact area is 0.5 mm. 2 The above, preferably 1.0mm 2 That's all. On the other hand, the average contact area mentioned above is 3.0 mm. 2 At the above points, the droplet adhesion distribution becomes uneven, increasing the bias in the delayed fracture evaluation. Therefore, the average contact area is less than 3.0 mm. 2 The preferred average contact area is 2.8 mm. 2The following is more preferably 2.5mm 2 It should be noted that the average contact area of ​​the droplets on the evaluation surface of the aforementioned metallic material can be determined by the measurement method described later.

[0194] <The total contact area of ​​the droplets relative to the area of ​​the evaluation surface of the metallic material: 40%–80%>

[0195] In the evaluation method of the present invention, at least in the first chloride adhesion step (A), the area ratio (total contact area ratio of droplets) of the total contact area of ​​the droplets relative to the area of ​​the evaluation surface of the metal material is 40% to 80%. When the total contact area ratio of the droplets is less than 40%, the droplet adhesion distribution becomes uneven, and the deviation in the delayed fracture evaluation increases. Therefore, the total contact area ratio of the droplets is 40% or more. Preferably, the total contact area ratio of the droplets is 50% or more, more preferably 55% or more. On the other hand, when the total contact area ratio of the droplets is greater than 80%, adjacent droplets on the evaluation surface tend to combine with each other, and the average contact area of ​​the droplets (average contact area per droplet) tends to become coarser. Therefore, the total contact area ratio of the droplets is 80% or less. Preferably, the total contact area ratio of the droplets is 75% or less, more preferably 70% or less. It should be noted that the total contact area ratio of the droplets can be measured by the measurement method described later.

[0196] Standard deviation of the contact area of ​​droplets on the evaluation surface of metallic materials: 3.0 mm 2 Following>

[0197] In the evaluation method of the present invention, at least in the first chloride adhesion step (A), the standard deviation of the distribution of the contact area of ​​the droplets on the evaluation surface of the metal material is 3.0 mm. 2 The standard deviation of the contact area of ​​the droplets on the evaluation surface of the metallic material is greater than 3.0 mm. 2 At this point, the droplet adhesion distribution becomes uneven, increasing the bias in the delayed fracture evaluation. Therefore, the standard deviation of the contact area of ​​the aforementioned droplets is 3.0 mm. 2 The standard deviation of the contact area of ​​the droplets described above is preferably 2.8 mm. 2 The following is more preferably 2.5mm 2 It should be noted that the standard deviation of the contact area of ​​the droplets described above can be determined by the measurement method described later.

[0198] The droplet distribution of brine adhering to the evaluation surface of the metal material (average contact area of ​​droplets, total contact area ratio of droplets, standard deviation of droplet contact area) can be obtained by attaching brine droplets to the evaluation surface of the metal material in the chloride adsorption process (A), acquiring an image of the overall droplet distribution of the evaluation surface of the metal material, and performing image analysis. As a method for acquiring the above image, a digital camera, microscope, optical microscope, etc., can be used. Furthermore, the above image can be obtained from above the evaluation surface of the metal material (from...). Figure 2 The evaluation surface is obtained by photographing the metal material in the direction of the spray nozzle shown. The photographing of the evaluation surface can be performed inside the test chamber equipped with the spray nozzle, or after the metal material has been removed from the test chamber. Preferably, the metal material is removed from the test chamber equipped with the spray nozzle, and the evaluation surface of the metal material is photographed, as in the latter case. Furthermore, the image is obtained immediately after the salt water droplets adhere to the evaluation surface of the metal material (within 30 seconds).

[0199] Figure 3 This is a schematic diagram showing the distribution of droplets on the evaluation surface of the metallic material obtained as described above. Figure 3 In the image, the area represented by a circle represents the contact area of ​​the droplets. From such an image, the average contact area of ​​the droplets (the average contact area of ​​each droplet), the total contact area ratio of the droplets, and the standard deviation of the contact area of ​​the droplets can be obtained through image analysis.

[0200] Here, the evaluation surface for metallic materials refers to the surface used to evaluate the delayed fracture characteristics of metallic materials. This evaluation surface can be appropriately determined based on the metallic material being evaluated. For example, if the metallic material is a sheet metal, the surface of the sheet metal opposite the spray nozzle can be used as the evaluation surface (see [reference]). Figure 2 Furthermore, when stress is applied to the metal material, the surface of the stressed area opposite the spray nozzle (equivalent to the plane view (top view) of the metal material when the direction relative to the direction where the spray nozzle is located is taken as upward) can be used as the evaluation surface. More specifically, for example, when evaluating a metal material that has undergone bending, as described later, the surface of the bent area opposite the spray nozzle can be used as the evaluation surface (see...). Figure 8 ).

[0201] As a method for achieving the distribution of the aforementioned brine droplets, as described above, one example is using a spray nozzle to adhere the brine to the evaluation surface of a metal material. A two-fluid nozzle is preferred as the spray nozzle. Examples of two-fluid nozzles include KSMMS (product name) manufactured by Kyoritsu Alloy Manufacturing Co., Ltd., a two-fluid air atomizing nozzle (product name) manufactured by Spraying Systems Japan Co., Ltd., and a micro-mist generating nozzle (product name) manufactured by Ikenai Co., Ltd.

[0202] As an example of specific conditions when using a spray nozzle, the distance from the tip of the spray nozzle to the evaluation surface of the metal material ( Figure 2 The X value is preferably 10–30 cm. The spray pressure of the spray nozzle is preferably 0.05–0.7 MPa. The spray angle ( Figure 2 The angle θ is preferably 30–120°. The spraying time of the brine is preferably less than 10 seconds. Furthermore, as mentioned above, the chloride concentration in the brine is preferably adjusted according to the amount of chloride adhering to the target. It should be noted that, for example… Figure 8 As shown, when the metal material that has undergone bending is used as the evaluation object, the distance from the tip of the spray nozzle to the evaluation surface of the metal material refers to the shortest distance from the tip of the spray nozzle to the evaluation surface of the metal material.

[0203] As a method for distributing the aforementioned brine droplets, the following method is particularly preferred: a shielding material with an opening is disposed between a spray nozzle and a metal material, through which droplets of the chloride-containing aqueous solution sprayed from the spray nozzle adhere to the evaluation surface of the metal material. Preferably, the opening of the shielding material has a shape and size substantially the same as the evaluation surface of the metal material. It should be noted that "substantially the same" means that the opening of the shielding material is identical in shape and size to the outer periphery of the evaluation surface when viewed from the spray side, or that the area of ​​the opening of the shielding material is within ±10% of the area of ​​the evaluation surface of the metal material. Furthermore, the shielding material is preferably configured to shield the portion of the metal material other than its evaluation surface. That is, the shielding material is preferably configured such that when viewed from above, the evaluation surface of the metal material is visible through the opening of the shielding material, while other portions are not visible (are shielded).

[0204] Figure 4 This is a schematic diagram illustrating the case where a shielding material is disposed between the spray nozzle and the metal material in the evaluation method of the present invention. (See diagram for example.) Figure 4As shown, by placing the aforementioned shielding material between the spray nozzle and the metal material, it is possible to suppress the spray liquid (atomized brine) that, although ejected from the spray nozzle, does not adhere to the evaluation surface of the metal material and floats in the atmosphere, from adhering to (re-adhering to) the evaluation surface of the metal material with attached droplets after the brine spraying is completed. As a result, the desired droplet distribution on the evaluation surface of the metal plate can be achieved with high precision.

[0205] When using a masking material, the distance X from the tip of the spray nozzle to the evaluation surface of the metal material is preferably 10 to 30 cm. Furthermore, it is preferable to keep the distance between the masking material and the evaluation surface of the metal material (…). Figure 4 The distance Y in the figure is 1 cm to 0.3X cm. When the distance Y is less than 1 cm, the spray liquid that did not adhere to the evaluation surface of the metal material but floated in the atmosphere remained near the evaluation surface of the metal material, thus reducing the inhibition effect of re-adhesion. Figure 5 (a)). On the other hand, when the distance Y is greater than 0.3X cm, the spray liquid passing through the opening of the shielding material disperses below the shielding material, and the re-adhesion suppression effect becomes smaller. Figure 5 (b) It should be noted that the aforementioned distance Y is the shortest distance from the shielding material to the evaluation surface of the metallic material. It should also be noted that the material of the shielding material is not limited as long as it can prevent the penetration of the sprayed liquid. Examples of materials include resin, ceramics, metals, and wood. These materials can be processed and used as shielding materials.

[0206] As described above, in the evaluation method of the present invention, it is important to uniformly control the distribution of brine droplets on the evaluation surface of the metal material in the initial (first) chloride adhesion process (A), and to implement the droplet distribution control on the evaluation surface as described above at least in the initial chloride adhesion process (A). Furthermore, the average contact area of ​​the droplets, the total contact area ratio of the droplets, and the standard deviation of the droplet contact area can be measured at the end of the initial chloride adhesion process (A) (within 30 seconds after the brine spray ends). Alternatively, a different test body than the test body provided for testing can be used beforehand, and the conditions can be set in a manner that defines the average contact area of ​​the droplets, the total contact area ratio of the droplets, and the standard deviation of the droplet contact area, and the evaluation test of the test body can be performed under the same conditions. It should be noted that in subsequent chloride adhesion processes (A), chloride adhesion can be performed under the same conditions as in the initial chloride adhesion process (A), or, if a specified chloride adhesion amount can be obtained, chloride adhesion can be performed under different conditions than in the initial chloride adhesion process (A). Preferably, the initial chloride adsorption process (A) is performed under pre-set conditions that define the average contact area of ​​the droplets, the total contact area ratio of the droplets, and the standard deviation of the contact area of ​​the droplets. Furthermore, when performing the chloride adsorption process (A) two or more times, it is preferable to perform the subsequent chloride adsorption processes (A) under the same pre-set conditions.

[0207] The chloride adhesion process (A) is preferably carried out in an atmosphere with a relative humidity Ha1 of 30% or higher. When the relative humidity Ha1 in the chloride adhesion process (A) is less than 30%, especially when using a spray nozzle to spray droplets containing an aqueous solution of chloride, the droplets sprayed from the spray nozzle tend to dry out before reaching the evaluation surface of the metal material. As a result, it is sometimes difficult to control the droplet distribution to achieve the desired effect on the evaluation surface of the metal material. Furthermore, the chloride adhesion process (A) is preferably carried out in an atmosphere with a relative humidity of 80% or lower. If the relative humidity in the chloride adhesion process (A) is greater than 80%, the droplets adhering to the metal material tend to become coarse.

[0208] Furthermore, the chloride adsorption process (A) is preferably carried out in an atmosphere with a temperature Ta1 below 50°C. When the temperature Ta1 in the chloride adsorption process (A) exceeds 50°C, especially when using a spray nozzle to spray droplets containing an aqueous solution of chloride, the droplets sprayed from the spray nozzle tend to dry out before reaching the evaluation surface of the metal material. As a result, it is sometimes difficult to control the droplet distribution to achieve the desired effect on the evaluation surface of the metal material. On the other hand, there is no limit to the lower limit of the temperature Ta1 as long as it is a temperature that can maintain the brine state. As an example, the lower limit of the temperature Ta1 is 25°C.

[0209] The atmospheric corrosion environment is characterized by repeated wetting (humid) and drying (dry) states, and simulating the corrosion morphology in a manner close to that of a real-world automotive environment is important. For example, in the case of steel, it is known that corrosion products formed on steel deteriorate due to wetting and drying states, and hydrogen is generated during the transition from a wetting to a drying state or vice versa. Therefore, the conditions within the cycle of relative humidity change (corrosion process (B)) are also important in evaluating delayed fracture characteristics.

[0210] (Etching process (B))

[0211] The etching process (B) is a process performed at least once (or twice) in an atmosphere at a temperature Tb1 below 60°C and within a certain range, consisting of the following cycles: drying process (b1), wetting process (b2), transition process (b3), and transition process (b4).

[0212] <Temperature Tb1 of corrosion process (B): below 60℃ and within a certain range>

[0213] The corrosion process (B) is carried out in an atmosphere with a temperature Tb1 below 60°C and within a certain range. It is considered that if the temperature Tb1 of the corrosion process (B) exceeds 60°C, not only will the evaluation be conducted in an environment deviating from the actual corrosion environment of the metal material being used, but the corrosion mechanism will also change. Therefore, the temperature Tb1 of the corrosion process (B) is below 60°C, preferably below 50°C. On the other hand, there is no particular limitation on the lower limit of the temperature Tb1 of the corrosion process (B). If the temperature Tb1 of the corrosion process (B) is less than 5°C, it is sometimes difficult to control the relative humidity in the corrosion test tank (constant temperature and humidity tank) used during the corrosion test. Furthermore, the evaluation time becomes longer because the corrosion rate of the metal material decreases significantly. Therefore, the temperature Tb1 of the corrosion process (B) is preferably 5°C or higher, more preferably 10°C or higher.

[0214] Furthermore, delayed fracture characteristics are strongly affected by the temperature of the environment (atmosphere). Therefore, in order to properly evaluate the delayed fracture characteristics of metallic materials considering the application location and operating environment of the metallic component, it is necessary to control the temperature Tb1 of the aforementioned corrosion process (B) within a certain range. When the temperature Tb1 of the corrosion process (B) varies within ±5°C, the amount of hydrogen penetrating into the interior of the metallic material from the environment (hydrogen intrusion amount) can be evaluated with a variation of less than 30% relative to the hydrogen intrusion amount at the target ambient temperature, thus accurately evaluating the delayed fracture characteristics. When the temperature Tb1 of the corrosion process (B) fluctuates within ±2°C, the variation of hydrogen intrusion amount is within 15%. Therefore, the temperature Tb1 of process (B) is preferably within ±5°C, and more preferably within ±2°C.

[0215] [Drying process (b1)]

[0216] The drying process (b1) involves drying the metal material in an atmosphere with a relative humidity (Hb1) of 45% or less for 1.0 to 5.0 hours. The relative humidity (Hb1) in the drying process (b1) is 45% or less. This is to simulate a drying state, which is one of the characteristics of an atmospheric corrosion environment. Furthermore, if the relative humidity (Hb1) in the drying process (b1) exceeds 45%, a longer holding time is required to ensure sufficient drying of the metal material surface, thus increasing the evaluation time. The relative humidity (Hb1) in the drying process (b1) is preferably 40% or less. On the other hand, there is no particular limitation on the lower limit of the relative humidity (Hb1) in the drying process (b1). From the viewpoint of controlling relative humidity, the relative humidity (Hb1) in the drying process (b1) is preferably 20% or more. Moreover, when the components adhering to the surface of the metal material contain substances such as magnesium chloride or calcium chloride that exhibit deliquescence at lower relative humidity, it is preferable to set the relative humidity (Hb1) in the drying process (b1) to be lower.

[0217] The drying process (b1) has a processing time of 1.0 to 5.0 hours (the time it is held in an atmosphere with a relative humidity of Hb1). If the drying process (b1) has a processing time of less than 1.0 hour, it is impossible to simulate the actual corrosive environment. On the other hand, if the drying process (b1) has a processing time of more than 5.0 hours, although it is possible to simulate the actual corrosive environment, the evaluation of delayed fracture characteristics will be time-consuming.

[0218] [Wetting process (b2)]

[0219] The wetting process (b2) involves wetting the metal material for 1.0 to 5.0 hours in an atmosphere with a relative humidity (Hb2) of 80% or higher. The relative humidity (Hb2) of the wetting process (b2) is 80% or higher. This is to simulate the wetting state, which is one of the characteristics of an atmospheric corrosion environment. If the relative humidity (Hb2) of the wetting process (b2) is less than 80%, the wetting effect is insufficient, and the actual corrosion environment cannot be simulated. Among chlorides, sodium chloride has the highest saturated critical vapor pressure, which is approximately 75-78% when converted to relative humidity. Therefore, regardless of the type of chloride, as long as the relative humidity is maintained above 80%, a water film will form on the surface of the metal material due to the hygroscopic absorption of the chloride, maintaining a wetted state. Therefore, the relative humidity (Hb2) of the wetting process (b2) is 80% or higher. On the other hand, there is no particular upper limit to the relative humidity (Hb2) of the wetting process (b2), but it is preferable to have a relative humidity (Hb2) of less than 98%. This is because if the relative humidity Hb2 reaches 98% or higher, the resulting water film from condensation will be too thick, making it easy for attached chlorides to be washed away. This phenomenon is particularly likely to occur when evaluating processed test subjects. Therefore, when evaluating processed test subjects, the relative humidity Hb2 of the wetting process (b2) is preferably less than 98%.

[0220] The processing time for the wetting process (b2) (the time maintained in an atmosphere of Hb2 with a relative humidity of 80% or higher) is 1.0 hour to 5.0 hours. If the processing time for the wetting process (b2) is less than 1.0 hour, it is impossible to simulate the actual corrosive environment. On the other hand, if the processing time for the wetting process (b2) exceeds 5.0 hours, although it is possible to simulate the actual corrosive environment, the evaluation of delayed fracture characteristics will be time-consuming.

[0221] [Transition process (b3), transition process (b4)]

[0222] Transition process (b3) is the process of transitioning from an atmosphere with relative humidity Hb1 to an atmosphere with relative humidity Hb2, and transition process (b4) is the process of transitioning from an atmosphere with relative humidity Hb2 to an atmosphere with relative humidity Hb1. It is known that the amount of hydrogen penetrating into the interior of metallic materials, especially steel materials, increases when relative humidity changes. That is, in transition processes (b3) and (b4), a large amount of hydrogen penetrates into the interior of the steel material. While the reason for this increase in hydrogen penetration into the metallic material when relative humidity changes may not be entirely clear, it can be considered as follows: In the case of transition process (b3), where the atmosphere changes from Hb1 to Hb2, moisture is absorbed due to the deliquescence of chlorides present on the surface of the metallic material, and corrosion of the metallic material begins. It is known that the corrosion products present on the surface of the metallic material change at this time, and it is assumed that hydrogen is generated simultaneously with this change in corrosion products. Furthermore, in the transition process (b4), where the atmosphere changes from Hb2 to Hb1, the moisture becomes a concentrated solution containing a large amount of chloride and metal ions dissolved from corrosion, specifically iron ions in the case of steel materials, and the pH of the solution is considered to decrease. That is, the solution in the drying process contains a large amount of hydrogen ions, and hydrogen is considered to easily penetrate the metal material. Therefore, in the transition processes (b3) and (b4), the rate of change of relative humidity is kept to 30% / h or less. As long as the rate of change of relative humidity in the transition processes (b3) and (b4) is 30% / h or less, hydrogen generated during corrosion can sufficiently penetrate the metal material, thereby allowing for appropriate evaluation of delayed fracture characteristics. On the other hand, there is no specific requirement for a lower limit to the rate of change of relative humidity. If the transition processes (b3) and (b4) are too long, evaluating the delayed fracture characteristics will require a longer time; therefore, the rate of change of relative humidity is preferably 1.5% / h or more, and more preferably 10% / h or more.

[0223] The purpose of the method for evaluating the delayed fracture characteristics of metallic materials according to the present invention is to simulate the diurnal variation of relative humidity in a real environment. Therefore, if the processing time (time of one cycle) of the corrosion process (B) simulating the diurnal variation of relative humidity in a real environment exceeds 24 hours, it means that corrosion is slower than in a real environment, thus requiring a longer time to evaluate the delayed fracture characteristics. That is, the processing time of the corrosion process (B) is preferably set to 24 hours or less. To facilitate evaluation, the processing time of the corrosion process (B) is more preferably set to 12 hours or less. On the other hand, if the processing time of the corrosion process (B) is shortened, the relative humidity changes drastically, reducing the correlation with corrosion in a real environment and resulting in inconsistencies with the delayed fracture characteristics observed in a real environment. Therefore, the processing time of the corrosion process (B) is preferably set to 5 hours or more.

[0224] In the evaluation method of the present invention, the chloride adhesion process (A) and the corrosion process (B) are performed at least once each. The chloride adhesion process (A) can be configured in each cycle of the corrosion process (B) at a random number of times, or it can be configured in each cycle of the corrosion process (B) at a predetermined number of times. It should be noted that there is no particular upper limit to the number of times the process including the chloride adhesion process (A) and the corrosion process (B) is performed. For example, the process including the chloride adhesion process (A) and the corrosion process (B) can be performed until cracks appear in the metal material. In addition, the number of test days can be predetermined, and the number of the above processes can be performed in a number equivalent to the number of test days. The number of the above processes can be appropriately set, for example, by considering the corrosion morphology in a real environment. As an example, the above processes can be set to 200 times or less, or 100 times or less.

[0225] Next, the process that includes the chloride adhesion process (A) and the corrosion process (B) will be described. Figure 6 This is a diagram illustrating one embodiment of the corrosion test cycle of the evaluation method of the present invention. Figure 6 The corrosion test cycle shown represents an example of a corrosion test cycle when performing one chloride adhesion process (A) and one corrosion process (B) respectively. In this example, the corrosion process (B) has a process that includes a drying process (b1), a transition process (b3), a wetting process (b2), and a transition process (b4) as one cycle.

[0226] The corrosion cycle following the chloride adhesion process (A) preferably begins with the drying process (b1). By drying the brine adhering to the chloride adhesion process (A) in the drying process (b1), the starting point of condensation is evenly dispersed when humidity rises, which can reduce the bias in the evaluation of delayed fracture characteristics. If the corrosion cycle (B) begins with a transition process (b3), a wetting process (b2), or a transition process (b4), the starting point of condensation is likely to be unevenly dispersed because the brine adhering to the chloride adhesion process (A) cannot be dried sufficiently, or the brine adhering to the chloride adhesion process becomes coarse due to moisture absorption in a high humidity environment. Therefore, it is preferable to avoid starting the corrosion cycle (B) from a process other than the drying process (b1).

[0227] In the case of a cycle of corrosion process (B) after chloride adhesion process (A) and chloride adhesion process (A) is performed again, it is preferable to add water washing process (C) before chloride adhesion process (A). Figure 7This diagram illustrates an example of a corrosion test cycle in which a corrosion process (B) is performed after a chloride deposition process (A), and a water washing process (C) is performed before the chloride deposition process (A) is repeated. If the chloride deposition process (A) is repeated without adding the water washing process (C), the amount of chloride deposited tends to increase, and the amount of chloride accumulated on the surface of the metal material tends to increase, sometimes making it impossible to continue in the same corrosion environment. Therefore, it may be necessary to evaluate the delayed fracture characteristics under an environment different from the intended corrosion environment. Therefore, it is preferable to add a water washing process (C) before repeating the chloride deposition process (A). It should be noted that the water washing process (C) is a process of washing the evaluation surface of the metal material. The water washing method in the water washing process (C) is not particularly limited; for example, methods such as spraying water onto the evaluation surface of the metal material from a spray nozzle or immersing the metal material in water to wash the evaluation surface can be used.

[0228] In the evaluation method of the present invention, a process consisting of one or more corrosion test cycles is performed, which includes the following steps: performing the chloride adhesion process (A) and corrosion process (B) as described above, and performing a water washing process (C) before performing the chloride adhesion process (A) again; then confirming the state of the metal material (the presence and extent of cracks in the metal material, etc.), and evaluating the delayed fracture characteristics of the metal material based on the confirmed state of the metal material.

[0229] Specifically, the steel plate of the present invention has a cracking period of 63 days or more under the following conditions in the evaluation method (HeTsAce) for the delayed fracture characteristics of the above-mentioned metallic materials.

[0230] Process (A)

[0231] Aqueous solutions containing chloride: 15% by mass NaCl aqueous solution was sprayed via a spray method.

[0232] Chloride adhesion amount (converted from solids): 10000 mg / m³ 2

[0233] Distance between nozzle and evaluation surface ( Figure 2 (X in the text): 30cm

[0234] The distance between the shielding material and the evaluation surface ( Figure 5 Y in (5cm)

[0235] Temperature: 22℃, Relative Humidity: 50%

[0236] The distribution of droplets on the evaluation surface; the average contact area of ​​the droplets: 1.3 mm. 2 Standard deviation of droplet contact area: 1.3 mm 2Total contact area ratio of droplets: 71%

[0237] Process (B)

[0238] Drying process (b1): Temperature: 30℃, Relative humidity: 40%, Holding time: 2.0 hours

[0239] Wetting process (b2): Temperature: 30℃, Relative humidity: 90%, Holding time: 2.0 hours

[0240] Transition process (b3) relative humidity change rate: 25% / h

[0241] Transition process (b4) relative humidity change rate: 25% / h

[0242] Temperature fluctuation range: within ±5℃

[0243] The water washing process (C) is a process of washing the evaluation surface of the metal material. There is no particular limitation on the water washing method in the water washing process (C). The evaluation surface is washed by spraying water from a spray nozzle onto the evaluation surface of the metal material.

[0244] • After the initial step (A) of the corrosion test cycle is performed, the distribution of droplets on the evaluation surface is confirmed. Subsequent steps (A) are performed under the same conditions as the initial step (A). Step (B) is performed in sequence as drying step (b1) → transition step (b3) → wetting step (b2) → transition step (b4), which is considered as one cycle. This cycle is repeated 4 times. Before step (A) is performed, a water washing step (C) is added. Then, step (A) is performed.

[0245] • Metallic material for evaluation: The obtained steel sheet was cut into 16mm × 75mm pieces with the long side perpendicular to the rolling direction to prepare test pieces. The gap during cutting was 15%. Next, a four-point bending test was performed according to ASTM (G39-99), with stresses equivalent to YS and TS applied to the bending apex of the test piece. Then, the aforementioned corrosion environment cycle (HeTsAce) was implemented for 63 days. After the test, each test piece was visually inspected for cracks. Samples without cracks after being subjected to stress equivalent to YS were considered to have excellent resistance to delayed fracture under corrosive conditions.

[0246] In the aforementioned evaluation method for delayed fracture characteristics of metallic materials (HeTsAce), there is a trend of low diffusible hydrogen content in steels that take a long time to develop cracks.

[0247] [Methods for manufacturing steel plates]

[0248] Next, the method for manufacturing the steel plate of the present invention will be described.

[0249] The steel plate manufacturing method of the present invention involves hot rolling, pickling, and cold rolling of steel having the above-mentioned composition to produce a cold-rolled sheet. The cold-rolled sheet is then subjected to an annealing process where it is heated at an annealing temperature T1 of 750°C to 850°C and a holding time t1 at the annealing temperature T1 of 10 seconds to 1000 seconds. Cooling is performed with an average cooling rate CR1 of 700 to 600°C set to less than 5°C / s, and an average cooling rate CR2 of 5°C is set to the quenching start temperature T2 from (Ms + 100°C) to (Ms - 50°C) or higher but less than (Ms + 50°C). Cooling at a rate of 30°C / s to 30°C / s and an average cooling rate CR3 of 300°C / s or more from the quenching start temperature T2 to 80°C, using water quenching, is performed under the conditions of a tempering temperature T3 of 100°C to 400°C and a holding time t3 of 10 seconds to 10000 seconds at the tempering temperature T3; in the water quenching cooling during the annealing process, pressure is applied from the surface and back of the steel plate by two rollers that clamp the steel plate, and this pressure is performed under the conditions that the distance between the rollers in the steel plate conveying direction of the two rollers is 20mm to 250mm and the pressure is 196N or more.

[0250] In this invention, the smelting method for the steel billet is not particularly limited, and known smelting methods such as converters or electric furnaces are suitable. To prevent macroscopic segregation, the steel billet (slab) is preferably manufactured by continuous casting.

[0251] In this invention, the slab heating temperature, slab soaking time, and coiling temperature during hot rolling are not particularly limited. Examples of methods for hot rolling steel billets include methods that heat the slab before rolling, methods that directly roll the slab without heating it after continuous casting, and methods that subject the continuously cast slab to short-time heat treatment before rolling.

[0252] There are no particular limitations on the slab heating temperature, slab soaking time, finishing rolling temperature, and coiling temperature during hot rolling. The preferred slab heating temperature is above 1100℃. The preferred slab heating temperature is below 1300℃.

[0253] The preferred slab heating time is 30 minutes or more. The preferred slab heating time is 250 minutes or less.

[0254] The finishing rolling temperature is preferably above the Ar3 phase transformation point.

[0255] Furthermore, the winding temperature is preferably 350°C or higher. Alternatively, the winding temperature is preferably 650°C or lower.

[0256] The hot-rolled steel sheets manufactured in this way are pickled. Pickling removes oxides from the surface of the steel sheet; therefore, it is important to ensure good chemical conversion properties and coating quality of the final high-strength steel sheet. Furthermore, pickling can be performed in one step or in multiple steps. Additionally, cold rolling can be carried out while the hot-rolled and pickled sheet is still in the same state, or cold rolling can be performed after heat treatment.

[0257] The reduction rate (cumulative reduction rate) during cold rolling and the thickness of the rolled plate are not particularly limited, but the reduction rate is preferably 30% or more. Furthermore, the reduction rate is preferably 80% or less. It should be noted that the effects of the present invention can be obtained without particular limitation on the number of rolling passes or the reduction rate of each pass.

[0258] The cold-rolled sheet obtained as described above is then annealed. The annealing conditions are as follows.

[0259] Annealing temperature T1: 750℃~850℃

[0260] When the annealing temperature T1 is less than 750℃, the combined area fraction of ferrite and bainitic ferrite is more than 15%, making it difficult to achieve YR≥65%.

[0261] On the other hand, when the annealing temperature T1 exceeds 850℃, the combined area fraction of ferrite and bainitic ferrite is less than 5%, making it difficult to achieve excellent ductility. Therefore, the annealing temperature T1 is 750℃~850℃.

[0262] The annealing temperature T1 is preferably 760°C or higher, more preferably 770°C or higher. The annealing temperature T1 is preferably 840°C or lower, more preferably 830°C or lower. The annealing temperature referred to here is the holding temperature during the annealing process. It should be noted that the annealing temperature can be constant during the holding period. Furthermore, as long as the annealing temperature is within the temperature range of 750°C to 850°C and the temperature variation is within ±10°C of the set temperature, it does not need to be constant throughout the holding period.

[0263] Holding time t1 at annealing temperature T1: 10 seconds to 1000 seconds

[0264] When the holding time t1 at the annealing temperature T1 is less than 10 seconds, the total area fraction of ferrite and bainitic ferrite is more than 15%, making it difficult to achieve YR≥65%.

[0265] On the other hand, when the holding time t1 at the annealing temperature T1 exceeds 1000 seconds, the combined area fraction of ferrite and bainitic ferrite is less than 5%, making it difficult to achieve excellent ductility. Therefore, the holding time t1 at the annealing temperature T1 is between 10 seconds and 1000 seconds. The holding time t1 at the annealing temperature T1 is preferably 30 seconds or more. The holding time at the annealing temperature T1 is preferably 800 seconds or less.

[0266] Average cooling rate CR1 between 700 and 600°C: less than 5°C / s

[0267] When the average cooling rate CR1 for 700–600°C is 5°C / s or higher, the total area fraction of ferrite and bainitic ferrite is less than 5%, making it difficult to achieve excellent ductility. Therefore, the average cooling rate CR1 for 700–600°C is set to be less than 5°C / s. The average cooling rate CR1 is preferably 3°C / s or lower. The lower limit is not particularly limited, but the average cooling rate CR1 is preferably 1°C / s or higher.

[0268] Here, the average cooling rate CR1 can be calculated by (cooling start temperature (700℃) - cooling stop temperature (600℃)) / cooling time (s) from cooling start temperature (700℃) to cooling stop temperature.

[0269] Cooling methods at an average cooling rate CR1 can include water cooling or spray cooling.

[0270] Average cooling rate CR2 (Ms + 100℃) ~ quenching start temperature T2: 5℃ / s ~ 30℃ / s

[0271] In this invention, this is one of the important inventive components. The average cooling rate CR2 from (Ms+100℃) to the quenching start temperature T2 affects the total area fraction of ferrite and bainitic ferrite, as well as the average occupancy of lath bundles with the maximum occupancy within the original austenite grains at the center of the steel plate thickness. When the average cooling rate CR2 from (Ms+100℃) to the quenching start temperature T2 is less than 5℃ / s, the total area fraction of ferrite and bainitic ferrite is more than 15%, making it difficult to achieve YR≥65%.

[0272] On the other hand, when the average cooling rate CR2 from (Ms+100℃) to the quenching start temperature T2 exceeds 30℃ / s, the average occupancy of lath bundles with the maximum occupancy of the original austenite grains at the center of the steel plate thickness exceeds 70%, resulting in decreased fatigue resistance at the shear end face and resistance to delayed fracture in corrosive environments. Therefore, the average cooling rate CR2 from (Ms+100℃) to the quenching start temperature T2 is set to 5℃ / s to 30℃ / s. The average cooling rate CR2 is preferably 10℃ / s or more. The average cooling rate CR2 is preferably 20℃ / s or less.

[0273] Here, the average cooling rate CR2 can be calculated by (cooling start temperature (Ms+100℃) - cooling stop temperature (quenching start temperature T2)) / cooling time (s) from cooling start temperature (Ms+100℃) to cooling stop temperature (quenching start temperature T2).

[0274] Cooling at an average cooling rate CR2 can be exemplified by spray cooling or gas cooling.

[0275] The temperature at which the rapid cooling begins, T2, is above (Ms - 50℃) and below (Ms + 50℃).

[0276] This is one of the important inventive elements in this invention. By setting the quenching start temperature T2 to be above (Ms-50°C) and below (Ms+50°C), it is possible to obtain a microstructure in which the average percentage of lath bundles with the maximum occupancy of the original austenite grains at the center of the steel plate thickness is 70% or less, and the retained austenite content is less than 3% by volume fraction. When the quenching start temperature T2 is less than (Ms-50°C), the retained austenite content is more than 3% by volume fraction, making it difficult to achieve a YR content of more than 65%.

[0277] On the other hand, when the quenching start temperature T2 is (Ms + 50°C) or higher, the average occupancy of lath bundles with the maximum occupancy of the original austenite grains at the center of the steel plate thickness exceeds 70%, and the fatigue resistance of the shear end face and the resistance to delayed fracture in corrosive environments decrease. Therefore, the quenching start temperature T2 is set to be (Ms - 50°C) or higher and lower than (Ms + 50°C). The quenching start temperature T2 is preferably (Ms - 40°C) or higher. The quenching start temperature T2 is preferably (Ms + 40°C) or lower. It should be noted that Ms is the martensitic transformation start temperature (°C), which is defined by the following formula (3).

[0278] Ms=519-474×[%C]-30.4×[%Mn]-12.1×[%Cr]-7.5×[%Mo]-17.7×[%Ni]····(3)

[0279] Here, [%C], [%Mn], [%Cr], [%Mo], and [%Ni] represent the content (mass%) of C, Mn, Cr, Mo, and Ni in the steel (steel plate), respectively, and 0 if they are not present.

[0280] Average cooling rate CR3 from quenching start temperature T2 to 80°C: 300°C / s or higher

[0281] When the average cooling rate CR3 from the quenching start temperature T2 to 80°C is less than 300°C / s, the retained austenite content, by volume fraction, is more than 3%, making it difficult to achieve a YR content of more than 65%. Therefore, the average cooling rate CR3 from the quenching start temperature T2 to 80°C is set to 300°C / s or more. The average cooling rate CR3 is preferably 800°C / s or more. There is no particular upper limit, but the average cooling rate CR3 is preferably 3000°C / s or less.

[0282] Here, the average cooling rate CR3 can be calculated as (cooling start temperature (quenching start temperature T2) - cooling stop temperature (80°C) / cooling time (s) from cooling start temperature (quenching start temperature T2) to cooling stop temperature (80°C).

[0283] Tempering temperature T3: 100℃~400℃

[0284] In this invention, tempered martensite refers to a microstructure in which martensite below 80°C has undergone heat treatment at a tempering temperature above 100°C and a holding time of at least 10 seconds. In the tempering process within the annealing process, if the tempering temperature T3 is less than 100°C, the martensite is not sufficiently tempered, resulting in a microstructure dominated by quenched martensite. This quenched martensite deteriorates the fatigue resistance of the shear end face.

[0285] On the other hand, when the tempering temperature T3 exceeds 400°C, excessive tempering of martensite occurs, making it difficult to achieve a TS of 1180 MPa or higher. Therefore, the tempering temperature T3 is set to 100°C to 400°C. Preferably, the tempering temperature T3 is 150°C or higher. Preferably, the tempering temperature T3 is 350°C or lower.

[0286] Holding time t3 at tempering temperature T3: 10 seconds to 10,000 seconds

[0287] In this invention, tempered martensite refers to a microstructure obtained by subjecting martensite below 80°C to a heat treatment at a tempering temperature above 100°C and a holding time of 10 seconds or more.

[0288] In the tempering process of annealing, if the holding time t3 at the tempering temperature T3 is less than 10 seconds, the martensite is not sufficiently tempered and becomes a structure dominated by quenched martensite. The quenched martensite will deteriorate the fatigue resistance of the shear end face.

[0289] On the other hand, when the holding time t3 exceeds 10,000 seconds, the tempering of martensite proceeds excessively, making it difficult to achieve a TS of 1180 MPa or higher. Therefore, the holding time t3 at the tempering temperature T3 is set to 10 to 10,000 seconds. The holding time t3 is preferably 50 seconds or more. The holding time t3 is preferably 5,000 seconds or less.

[0290] The cooling after tempering does not require special specifications and can be achieved by any method to cool to the desired temperature. It should be noted that the desired temperature is preferably around room temperature.

[0291] Furthermore, the aforementioned steel plate (high-strength steel plate) can be processed under conditions resulting in an equivalent plastic strain of 0.05% to 5.00%. Additionally, it can be reheated after processing to conditions of 100°C to 400°C.

[0292] It should be noted that when steel plates (high-strength steel plates) become the subject of trade, they are usually traded after being cooled to room temperature.

[0293] During water quenching, two rollers clamping the steel plate apply pressure from both the surface and back of the plate. The distance between the two rollers in the steel plate conveying direction is 20mm to 250mm, and the applied pressure is above 196N.

[0294] In the water quenching cooling process of the annealing process, two rollers clamping the steel plate apply pressure to the surface and back of the steel plate. At this time, the distance between the two rollers in the steel plate conveying direction (hereinafter referred to as the roller distance) is set to 20mm to 250mm, and the applied pressure is set to 196N or more. The "distance between the two rollers" mentioned in this invention refers to, for example... Figure 9 As shown, this is the distance between the contact points of one roller and the steel plate and the contact points of the other roller and the steel plate.

[0295] In the aforementioned water quenching process, without pressurization, P(S) becomes excessively large relative to P(C), making it difficult to satisfy {P(S) - P(C)} ≤ 20%, thus reducing the fatigue resistance of the sheared end face and the resistance to delayed fracture in corrosive environments. The inventors conducted repeated and in-depth research and found that applying pressure during the aforementioned water quenching process affects the difference between P(S) and P(C). By applying pressure at a distance of 20mm to 250mm between the two rollers and a pressure of 196N or more, the nucleation of martensitic phase transformation near the surface of the steel plate is promoted relative to the center of the steel plate, which helps to reduce {P(S) - P(C)}. Therefore, it is possible to achieve {P(S) - P(C)} ≤ 20%, improving the fatigue resistance of the sheared end face and the resistance to delayed fracture in corrosive environments. To achieve this effect, the roller distance (refer to...) Figure 9 It needs to be kept at least 20mm away.

[0296] On the other hand, when the roller spacing exceeds 250mm, the pressure decreases, therefore the roller spacing needs to be set below 250mm. Pressure is applied by clamping the rollers with a distance between them, and the required pressure to achieve the above effect is 196N or more. This pressure is equivalent to the load of one roller. That is, a pressure of 196N or more means that each of the two rollers applies pressure with a force of 196N or more.

[0297] As a pressure condition, a roller distance of 30 mm or more is preferred. A roller distance of 220 mm or less is also preferred.

[0298] Furthermore, the preferred applied pressure is 294 N or more. The preferred applied pressure is 4900 N or less.

[0299] Furthermore, the pressure applied varies depending on the strength and tension of the steel plate. The pressure applied can be adjusted by the tension or the amount of pressure applied. The pressure applied within the above range can be confirmed by a load cell attached to the roll, and the amount of pressure applied can be calculated based on the roll diameter and roll position.

[0300] Based on the above, in the present invention, during water quenching (water cooling), two rollers that clamp the steel plate apply pressure from the surface and back of the steel plate. This pressure is applied under the condition that the distance between the two rollers is 20mm to 250mm and the pressure is 196N or more.

[0301] Furthermore, any plating treatment can be applied to the steel sheet. There are no particular limitations on the plating treatment. Examples of plating treatments include hot-dip galvanizing, alloyed hot-dip galvanizing, and electroplating. Other plating treatments besides galvanizing include aluminum plating or alloy plating. Examples of alloy plating include hot-dip galvanizing-aluminum-magnesium alloy plating or electroplating Zn-Ni alloy plating. The processing conditions can all be carried out according to conventional methods. It should be noted that, as mentioned above, the plating treatment is preferably performed during the cooling process from the annealing temperature T1 to the quenching start temperature T2, or after the tempering process. For example, hot-dip galvanizing or alloyed hot-dip galvanizing is preferably performed during the cooling process from the annealing temperature T1 to the quenching start temperature T2. Furthermore, electroplating or electroplating Zn-Ni alloy plating is preferably performed after the tempering process. It should be noted that, from a productivity standpoint, when performing hot-dip galvanizing and alloyed hot-dip galvanizing, it is preferable to perform the aforementioned heating, annealing, and plating processes on a hot-dip galvanizing production line, i.e., a CGL (Continuous Galvanizing Line). After hot-dip galvanizing, wiping can be performed to adjust the quality per unit area of ​​the plating.

[0302] There are no particular limitations on conditions other than those described above; conventional methods can be used. According to the steel sheet manufacturing method of one embodiment of the present invention described above, a steel sheet with a TS of 1180 MPa or higher, a YR of 65% or higher, and excellent ductility, fatigue resistance at the shear end face, and resistance to delayed fracture in corrosive environments can be obtained. The obtained steel sheet can, for example, be suitable as a raw material for automotive components.

[0303] After annealing and plating, the material can be processed again under conditions where the equivalent plastic strain is 0.05% to 5.00. Alternatively, it can be reheated after processing under conditions where the temperature is 100°C to 400°C.

[0304] [Components and methods of manufacturing components]

[0305] Next, the components of the present invention and their manufacturing method will be described.

[0306] The component of the present invention is formed by performing at least one of forming and joining processes on the steel plate of the present invention. Furthermore, the manufacturing method of the component of the present invention includes a step of performing at least one of forming and joining processes on the steel plate of the present invention to form the component.

[0307] The steel sheet of the present invention has a tensile strength of 1180 MPa or higher, a YR of 65% or higher, and excellent ductility, fatigue resistance at the shear end face, and resistance to delayed fracture in corrosive environments. Therefore, components obtained using the steel sheet of the present invention also have a tensile strength of 1180 MPa or higher, a YR of 65% or higher, and excellent ductility, fatigue resistance at the shear end face, and resistance to delayed fracture in corrosive environments. Using components of the present invention allows for weight reduction. Therefore, components of the present invention are suitable, for example, for use in automotive structural components.

[0308] Forming processes can utilize conventional processing methods such as stamping without restriction. Furthermore, joining processes can utilize conventional welding methods such as spot welding and arc welding, as well as riveting and rivet joining without restriction.

[0309] Example

[0310] Steel with the composition shown in Table 1 (Table 1-1, Table 1-2) (the remainder being Fe and unavoidable impurities) is melted in a converter and produced into steel billets by continuous casting. The steel billets are then heated. Next, the steel billets are hot-rolled to produce hot-rolled steel sheets. The hot-rolled steel sheets are then pickled. Next, the hot-rolled sheets are cold-rolled to produce cold-rolled steel sheets. This prepares the billet steel sheets. The prepared billet steel sheets are then annealed under the conditions shown in Table 2 (Table 2-1, Table 2-2) to obtain the final product steel sheet (plate thickness: 1.4 mm). Furthermore, a portion of the steel sheets (steel sheets with GI, GA, and EG in the type column of Table 2) undergoes a plating treatment. Specifically, for steel sheets with GI and GA in the type column of Table 2, plating is performed during the cooling period from the annealing temperature T1 to the quenching start temperature T2. Furthermore, for steel sheets with EG in the type column of Table 2, plating is performed after the tempering process. Conditions not explicitly stated shall be handled using standard methods.

[0311]

[0312]

[0313]

[0314]

[0315] The steel plate (high-strength cold-rolled steel plate) obtained as described above was used as the test steel. The tensile properties, fatigue resistance of the shear end face, and resistance to delayed fracture in corrosive environments were evaluated according to the following test methods.

[0316] (Organizational observation)

[0317] Using the method described above, calculate the total amount of tempered martensite (area fraction), retained austenite (volume fraction), ferrite, and bainite ferrite (area fraction).

[0318] (P(S): The average occupancy of lath bundles with the maximum occupancy within the original austenite grains at a depth of 100 μm from the surface of the steel plate; P(C): The average occupancy of lath bundles with the maximum occupancy within the original austenite grains at the center of the thickness of the steel plate.)

[0319] The average occupancy of lath bundles with the maximum occupancy within the original austenite grains was calculated using the method described above, at a depth of 100 μm from the surface of the steel plate and at the center of the plate thickness.

[0320] (Tension test)

[0321] In the tensile test, JIS No. 5 test pieces (marking distance 50 mm, parallel section width 25 mm) were used with the long side of the test piece perpendicular to the rolling direction as the long side, and the test was conducted according to JIS Z 2241 (2022). The crosshead speed was 1.67 × 10⁻⁶. -1 A tensile test is conducted under the condition of mm / s to determine the tensile strength TS. It should be noted that in this invention, a TS of 1180 MPa or higher is considered acceptable. A yield ratio YR of 65% or higher is considered acceptable. It should be noted that YR is calculated by the following formula (4).

[0322] YR = 100 × YS / TS ···(4)

[0323] Ductility is evaluated based on TS×El, and TS×El = 14000MPa·% or higher is considered qualified.

[0324] (Fatigue resistance properties of the shear end face)

[0325] The fatigue resistance of the shear end face was evaluated by a fully alternating bending test according to JIS Z 2275 (1978). The test shape was a punched hole with a diameter of Φ10 mm and a clearance of 12% made in the center of the fatigue test piece as described in JIS Z 2275 (1978). The resulting test piece was subjected to a fully alternating bending fatigue test with a constant stress amplitude (stress ratio R = -1), with 1 × 10⁻⁶ repetitions. 7The upper limit of the fatigue strength at the next time step is used as the fatigue limit of the shear end face to determine the fatigue strength ratio of the shear end face obtained by the following formula (5).

[0326] Fatigue strength ratio of shear end face = fatigue limit of shear end face / TS····(5)

[0327] Then, the fatigue resistance characteristics of the shear end face are evaluated based on the following criteria.

[0328] ◎ (Qualified, Excellent): Fatigue strength ratio of the shear end face is above 0.30.

[0329] ○ (Qualified, Excellent): The fatigue strength ratio of the shear end face is greater than 0.25 and less than 0.30.

[0330] × (Unacceptable): Fatigue strength ratio of the shear end face is less than 0.25.

[0331] (Resistance to delayed fracture in corrosive environments)

[0332] The obtained steel plate was cut into 16mm × 75mm pieces with the long side perpendicular to the rolling direction to prepare test specimens. The gap during cutting was 15%. Next, a four-point bending test was performed according to ASTM (G39-99), with the bending apex of the test specimen subjected to a stress equivalent to YS and TS. Then, a delayed fracture test was conducted using the corrosion environment cycling described later.

[0333] (Corrosion test cycle)

[0334] The test pieces described above are subjected to a corrosion test cycle (corrosion test) consisting of the following chloride adhesion process (A), corrosion process (B), and water washing process (C).

[0335] In the chloride adhesion process (A), the amount of chloride adhered (converted from solid content) is 10000 mg / m³. 2 The method of adhering droplets containing chloride aqueous solution. The distance between the spray nozzle and the evaluation surface of the test piece ( Figure 2 X in the figure is 30 cm. The spray pressure of the spray nozzle is 0.2 MPa. The spraying time of the brine is 5 seconds. The amount of chloride adhering is calculated by dividing the mass difference of the test piece before and after the brine spray by the evaluation surface area of ​​the test piece, and then by the chloride concentration of the brine solution.

[0336] In addition, the following conditions shall apply.

[0337] Aqueous solutions containing chloride: 15% by mass NaCl aqueous solution was sprayed via a spray method.

[0338] The distance between the shielding material and the evaluation surface ( Figure 5 Y in (5cm)

[0339] Temperature: 22℃, Relative Humidity: 50%

[0340] The distribution of droplets on the evaluation surface; the average contact area of ​​the droplets: 1.3 mm. 2 Standard deviation of droplet contact area: 1.3 mm 2 Total contact area ratio of droplets: 71%

[0341] It should be noted that subsequent chloride application processes (A) are performed under the same conditions as the initial chloride application process (A).

[0342] The etching process (B) consists of the following steps in sequence: drying process (b1) → transition process (b3) → wetting process (b2) → transition process (b4), and these four steps are considered as one cycle. It should be noted that in this embodiment, the temperature variation in the etching process (B) is within 30±5℃.

[0343] Drying process (b1): A process of drying metal materials under an atmosphere of 40% relative humidity (Hb1) for 2.0 hours.

[0344] Wetting process (b2): A process of wetting the metal material by maintaining an atmosphere of 90% relative humidity (Hb2) for 2.0 hours.

[0345] Transition process (b3): ​​A process that transitions from an atmosphere with relative humidity Hb1 to an atmosphere with relative humidity Hb2 at a relative humidity change rate of 25% / h.

[0346] Transition process (b4): A process that transitions from an atmosphere with relative humidity Hb2 to an atmosphere with relative humidity Hb1 at a relative humidity change rate of 25% / h.

[0347] The water washing process (C) is a process of washing the evaluation surface of the metal material. There is no particular limitation on the water washing method in the water washing process (C). Water is sprayed from a spray nozzle onto the evaluation surface of the metal material to wash the evaluation surface.

[0348] Furthermore, in this embodiment, a corrosion test cycle is adopted in which a corrosion process (B) is performed after the chloride adhesion process (A), and a water washing process (C) is performed before the chloride adhesion process (A) is performed again. That is, in this embodiment, the delayed fracture characteristics are evaluated using the following corrosion test cycle.

[0349] A cycle is repeated for the chloride deposition process (A) → corrosion process (B) → water washing process (C).

[0350] It should be noted that in this embodiment, the period for evaluating the resistance to delayed fracture using a corrosive environment cycle is 63 days.

[0351] After the test, the presence or absence of cracks in each test piece was visually inspected. Then, the resistance to delayed fracture under corrosive conditions was evaluated according to the following criteria. It should be noted that in this invention, the absence of cracks in a sample subjected to a stress equivalent to YS is considered an indication of excellent resistance to delayed fracture under corrosive conditions.

[0352] ◎ (Pass, Excellent): No cracks were found in the sample subjected to stresses equivalent to YS and TS.

[0353] ○ (Pass, Excellent): No cracks were found in the sample subjected to a stress equivalent to YS.

[0354] × (Unacceptable): Both samples subjected to stresses equivalent to YS and TS showed cracks.

[0355] In the examples of the present invention shown in Table 3 (Table 3-1, Table 3-2), the tensile strength TS is 1180 MPa or more, the yield ratio YR is 65% or more, and the ductility, fatigue resistance of the shear end face, and resistance to delayed fracture in corrosive environments are excellent. In contrast, at least one of the comparative examples is poor.

[0356] Furthermore, for components obtained by forming and joining using the steel plate of the present invention, since the tensile strength TS of the steel plate of the present invention is 1180 MPa or more, the yield ratio YR is 65% or more, and the ductility, fatigue resistance of the shear end face, and resistance to delayed fracture in corrosive environments are excellent, it can be seen that, similar to the steel plate of the present invention, its tensile strength is 1180 MPa or more, the yield ratio YR is 65% or more, and the ductility, fatigue resistance of the shear end face, and resistance to delayed fracture in corrosive environments are excellent.

[0357]

[0358]

Claims

1. A steel plate having the following composition: containing, by mass %: C: 0.030%–0.500%, Si: 0.010%–2.500%, Mn: 0.10%–5.00%, P: less than 0.100%, S: less than 0.0200%, Al: less than 1.000%, N: less than 0.0100%, and O: less than 0.0100%, the remainder consisting of Fe and unavoidable impurities. The steel plate has the following microstructure at 1 / 4 of its thickness: tempered martensite with an area fraction of 83% or more, retained austenite with a volume fraction of less than 3%, and a combined area fraction of ferrite and bainitic ferrite of 5% or more and less than 15%. The following equations (1) and (2) are satisfied. P(C)≤70%···(1) {P(S)-P(C)}≤20%···(2) In the formula, P(S): The average occupancy of lath bundles with the maximum occupancy within the original austenite grains at a depth of 100 μm from the surface of the steel plate. P(C): The average occupancy of lath bundles with the maximum occupancy within the original austenite grains at the center of the steel plate thickness.

2. The steel plate according to claim 1, wherein, The composition, by mass%, further contains at least one element selected from the following: Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Ni: 1.00% or less, Co: 0.010% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less, Bi: 0.200% or less.

3. The steel plate according to claim 1 or 2, wherein, The steel plate has a coating.

4. The steel plate according to any one of claims 1 to 3, wherein, In the evaluation of metallic materials, the crack duration is 63 days or more.

5. A component made of steel plate according to any one of claims 1 to 4.

6. A method for manufacturing a steel plate, comprising hot rolling, pickling, and cold rolling of steel having the composition described in claim 1 or 2 to produce a cold-rolled plate. The cold-rolled sheet is subjected to the following annealing process. Heating is performed at an annealing temperature T1 of 750℃~850℃ and a holding time t1 of 10 seconds~1000 seconds. Cooling with an average cooling rate CR1 of less than 5℃ / s from 700 to 600℃, cooling with an average cooling rate CR2 of 5℃ / s to 30℃ / s from a quenching start temperature T2 of (Ms+100℃) to (Ms-50℃) or higher but less than (Ms+50℃), and cooling using water quenching with an average cooling rate CR3 of 300℃ / s or higher from the quenching start temperature T2 to 80℃. Heating is performed under the following conditions: tempering temperature T3 is 100℃~400℃ and holding time t3 at tempering temperature T3 is 10 seconds~10000 seconds. In the water quenching cooling of the annealing process, two rollers that clamp the steel plate apply pressure from the surface and back of the steel plate. The pressure is applied under the condition that the distance between the rollers in the steel plate conveying direction is 20mm to 250mm and the pressure is 196N or more.

7. The method for manufacturing a steel plate according to claim 6, wherein, Implement plating treatment.

8. A method for manufacturing a component, comprising a step of performing at least one of forming and joining processes on a steel plate as described in any one of claims 1 to 4 to manufacture the component.